Gas barrier film, packaging film, and packaging bag
By using the substrate layer of polypropylene resin, steam coating layer of inorganic oxides, and gas -resistant gas -blocking gas -resistant membrane structures, the problem of heating and sterilization in the existing technology is difficult , Achieve efficient oxygen resistance and inter -layer tightness.
Patent Information
- Application Number
- CN202380039674.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-30
- Filing Date
- 2023-05-11
- Publication Date
- 2025-01-28
AI Technical Summary
The existing gas barrier film using polypropylene film is difficult to take into account the good oxygen barrier properties and interlayer adhesion after heating and sterilization.
The substrate layer containing a base material containing polypropylene resin, a steam coating layer containing inorganic oxides, and an air -resistant air -resistant gas obstruction film. The substrate layer has the first surface and core layer, and the hardness of the first surface layer is 0.02 ~ 0.15GPa, the hardness of the core layer is more than 0.07GPa.
After heating and sterilizing treatment, it still maintains good oxygen resistance and inter -layer density, and is suitable for packaging of food and pharmaceutical products.
Smart Images

Figure CN119384355A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a gas barrier film, a packaging film and a packaging bag. Background Art
[0002] Gas barrier films are widely used as packaging materials for food and medicines after being subjected to heat sterilization treatments such as boiling and retorting. When packaging food, medicines and other contents, it is important to reduce the oxygen permeability in order to suppress the deterioration and corruption of the contents and maintain their quality. Therefore, in the past, as a gas barrier film suitable for the above-mentioned purposes, a gas barrier film using a polyethylene terephthalate film substrate having heat resistance and low oxygen permeability was used.
[0003] However, as awareness of environmental issues increases, research is underway into packaging materials with gas barrier films that use a single raw material, so-called mono-material packaging materials, in order to improve recycling suitability. Polyolefin films such as polypropylene are commonly used as packaging materials, so in order to produce mono-material packaging materials, polyolefin films are also required as base materials with a thin gas barrier.
[0004] Polypropylene film as a polyolefin film has excellent transparency, mechanical strength, heat resistance, etc. Therefore, it has been studied to use polypropylene film as a base material of a gas barrier film. For example, in the following patent document 1, a method of mixing an ethylene-α-olefin copolymer in a polypropylene film is proposed, and in patent documents 2 and 3, a method of laminating different polypropylene films is proposed.
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Laid-Open No. 63-291929
[0008] Patent Document 2: Japanese Patent Application Laid-Open No. 63-290743
[0009] Patent Document 3: Japanese Patent No. 2969657 Summary of the invention
[0010] Problems to be solved by the invention
[0011] However, it is difficult for conventional gas barrier films using polypropylene films to achieve both good oxygen barrier properties and good interlayer adhesion after heat sterilization.
[0012] One aspect of the present disclosure aims to provide a gas barrier film having a polypropylene-based substrate and having good oxygen barrier properties and interlayer adhesion after heat sterilization. Another aspect of the present disclosure aims to provide a packaging film and a packaging bag using the gas barrier film.
[0013] Means for solving problems
[0014] One aspect of the present disclosure is to provide a gas barrier film, which comprises, in sequence, a substrate layer containing a polypropylene resin, a vapor-deposited layer containing an inorganic oxide, and a gas barrier coating layer, wherein the substrate layer comprises a first surface layer and a core layer, the vapor-deposited layer is formed on the side of the first surface layer, the hardness of the first surface layer measured by a nanoindentation method is 0.02 to 0.15 GPa, the hardness of the core layer is above 0.07 GPa, and the hardness of the core layer is greater than that of the first surface layer.
[0015] The gas barrier film has a polypropylene-based substrate and can achieve both good oxygen barrier properties and interlayer adhesion after heat sterilization.
[0016] In one aspect, the first skin layer may contain a propylene-α-olefin copolymer.
[0017] In one embodiment, the ratio of the thickness of the first skin layer to the thickness of the core layer may be 1 / 100 to 1 / 5.
[0018] In one embodiment, the complex elastic modulus of the first surface layer measured by nanoindentation may be 1.2 to 2.5 GPa, and the complex elastic modulus of the core layer may be 2.0 GPa or more.
[0019] In one form, the inorganic oxide may contain at least one of aluminum oxide and silicon oxide.
[0020] In one embodiment, the gas barrier coating layer may be formed of a cured product of a composition containing a water-soluble polymer having a hydroxyl group and at least one selected from the group consisting of a metal alkoxide, a silane coupling agent, and hydrolyzates thereof.
[0021] In one embodiment, the gas barrier film may further include an anchor coating layer between the substrate layer and the vapor-deposited layer.
[0022] In one form, the base material layer may include a first skin layer, a core layer, and a second skin layer in this order.
[0023] In one aspect, the second skin layer may contain a propylene-α-olefin copolymer.
[0024] In one embodiment, the hardness of the second surface layer measured by nanoindentation may be 0.02 to 0.15 GPa.
[0025] In one embodiment, the thickness of the vapor-deposited layer may be 5 nm to 80 nm.
[0026] Another aspect of the present disclosure provides a packaging film comprising: the above-mentioned gas barrier film, a sealing layer overlapping the gas barrier coating layer, and an adhesive layer bonding the gas barrier coating layer and the sealing layer, wherein the hardness of the adhesive layer measured by a nanoindentation method after the packaging film is subjected to a retort treatment is 0.1 MPa or more and less than 0.9 MPa.
[0027] In one embodiment, before the retort treatment, the adhesive layer may have a hardness of 1.0 MPa or more as measured by nanoindentation.
[0028] In one embodiment, the thickness of the adhesive layer may be 0.5 μm to 10 μm.
[0029] In one embodiment, the base layer and the sealant layer are each a polyolefin film, and the total mass ratio of the polyolefin in the packaging film may be 90 mass % or more.
[0030] In one embodiment, the substrate layer is a stretched polypropylene film, and the sealing layer can be an unstretched polypropylene film.
[0031] In one embodiment, the packaging film further comprises an outermost layer overlapping the substrate layer, and a second adhesive layer bonding the outermost layer to the substrate layer, wherein the adhesive layer bonds the substrate layer to the sealant layer, and the second adhesive layer can bond the substrate to the outermost layer.
[0032] In one embodiment, after the outermost layer is exposed to 120° C. for 15 minutes, the heat shrinkage of the outermost layer in the MD direction calculated by the following formula (1) is 1% or more, and after the packaging film is subjected to a retort treatment, the hardness of the second adhesive layer measured by a nanoindentation method can be 0.1 MPa or more and less than 0.9 MPa.
[0033] Heat shrinkage in MD direction (%) = (MD direction length before heating - MD direction length after heating) / MD direction length before heating × 100 (1)
[0034] One aspect of the present disclosure provides a packaging bag, which is a bag-made product of the packaging film.
[0035] Effects of the Invention
[0036] According to one aspect of the present disclosure, a gas barrier film having a polypropylene-based substrate and having good oxygen barrier properties and interlayer adhesion after heat sterilization can be provided. In addition, according to one aspect of the present disclosure, a packaging film and a packaging bag using the gas barrier film can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 It is a schematic cross-sectional view showing the gas barrier film according to the first embodiment.
[0038] Figure 2It is a schematic cross-sectional view showing a gas barrier film according to a modified example of the first embodiment.
[0039] Figure 3 It is a schematic cross-sectional view showing the packaging film according to the first embodiment.
[0040] Figure 4 It is a schematic cross-sectional view showing a packaging film according to a modified example of the first embodiment.
[0041] Figure 5 is a diagram showing a laminated body according to a second embodiment, Figure 5 (a) is a schematic plan view of a laminated body according to a second embodiment, Figure 5 (b) is a schematic cross-sectional view showing a laminated body according to the second embodiment.
[0042] Figure 6 It is a schematic front view of an example of a packaging bag according to the second embodiment.
[0043] Figure 7 It is a schematic cross-sectional view showing a stacked body according to a modified example of the second embodiment.
[0044] Figure 8 This is a schematic diagram showing a method for measuring the thermal shrinkage rate during oven heating. DETAILED DESCRIPTION
[0045] Hereinafter, embodiments of the present disclosure will be described in detail with reference to the accompanying drawings as appropriate. However, the present disclosure is not limited to the following embodiments.
[0046] [First embodiment]
[0047] <Gas Barrier Film>
[0048] Figure 1 Schematic cross-sectional view showing the gas barrier film of the first embodiment. Figure 1 As shown, the gas barrier film 10a includes a substrate layer 1, a vapor deposited layer 2, and a gas barrier coating layer 3 in this order. The substrate layer 1 has a first surface layer 11 and a core layer 12, and the vapor deposited layer 2 is formed on the first surface layer 11 side. That is, the vapor deposited layer 2 is formed on the first surface layer 11.
[0049] Figure 2 Schematic cross-sectional view of a gas barrier film showing a modified example of the first embodiment. Figure 2 As shown, the gas barrier film 10b includes a substrate layer 1, a vapor deposited layer 2, and a gas barrier coating layer 3 in this order. The substrate layer 1 has a first surface layer 11, a core layer 12, and a second surface layer 13, and the vapor deposited layer 2 is formed on the first surface layer 11 side. That is, the vapor deposited layer 2 is formed on the first surface layer 11.
[0050] [Base material layer]
[0051] The substrate layer is a film (base film) that becomes a support body, and contains a polypropylene resin. As the polypropylene resin, homopolypropylene and propylene copolymers can be listed. As the propylene copolymer, for example, polypropylene copolymers such as propylene-ethylene random copolymers, propylene-ethylene block copolymers, and propylene-α-olefin copolymers can be listed.
[0052] As the polypropylene resin, a recycled resin or a resin obtained by polymerizing a raw material from biomass such as plants can be used. These resins can be used alone or in combination with a resin polymerized from a common fossil fuel.
[0053] The substrate layer may be a stretched film or an unstretched film, but from the viewpoint of oxygen barrier properties, it may be a stretched film. Here, as the stretched film, single-screw stretched film and twin-screw stretched film can be listed, but the twin-screw stretched film can also improve heat resistance.
[0054] The substrate layer is, for example, a polyolefin film. In the present embodiment, the substrate layer may contain a polypropylene film or may be composed of a polypropylene film. The polypropylene film constituting the substrate layer may be a stretched film or an unstretched film. However, from the viewpoints of impact resistance, heat resistance, water resistance, dimensional stability, etc., the polypropylene film may be a stretched polypropylene film. Thus, the thermal fusion bonding of the substrate layer can be suppressed in the heat sealing process during bag making. In addition, in the application of heat treatment such as steaming treatment and boiling treatment, a gas barrier film can be more preferably used. There is no particular limitation on the stretching method, and any method can be used as long as it can provide a dimensionally stable film, such as stretching by blow molding, single-screw stretching, twin-screw stretching, etc.
[0055] The substrate layer may contain known additives, such as organic additives such as antioxidants, stabilizers, lubricants such as calcium stearate, fatty acid amide, erucic acid amide, and antistatic agents; and inorganic additives such as particulate lubricants such as silica, zeolite, silicates, hydrotalcite, and silicon particles.
[0056] The thickness (total thickness) of the substrate layer is not particularly limited, and may be, for example, 3 to 200 μm, or 6 to 50 μm.
[0057] From the viewpoint of heat resistance of the gas barrier film, the polypropylene resin contained in the core layer may be crystalline polypropylene. From the viewpoint of further improving heat resistance, the polypropylene resin contained in the core layer may be a homopolymer of propylene, i.e., homopolypropylene. The polypropylene resin contained in the core layer may also contain a mixture of homopolypropylene and a propylene-α-olefin random copolymer. The polypropylene resin contained in the core layer may contain more than 80% by mass of homopolypropylene, or may contain 100% by mass.
[0058] The first surface layer can alleviate the difference between the shrinkage stress of the core layer caused by heat sterilization and the shrinkage stress of the gas barrier coating layer, thereby preventing cracks in the gas barrier coating layer. Between the core layer and the first surface layer, another layer containing acid-modified polyolefin, ethylene-vinyl alcohol copolymer, polyamide, etc. and having an adhesive function can be provided, but the core layer and the first surface layer can also be in contact without the other layer.
[0059] In order to improve the adhesion between the base material layer and the vapor-deposited layer, the first surface layer (the vapor-deposited layer-side surface of the base material layer) may be subjected to a surface treatment such as a plasma treatment or a corona treatment.
[0060] The second surface layer can improve the lamination strength with the adjacent layer (outer film or sealing layer). Other layers similar to the above can also be provided between the core layer and the second surface layer. Alternatively, the core layer and the second surface layer can be in contact without other layers.
[0061] In order to improve the lamination strength with the adjacent layers without providing the second skin layer, the surface of the core layer may be subjected to a surface treatment such as plasma treatment or corona treatment, or an easy-adhesion coating may be provided.
[0062] From the viewpoint of improving the adhesion with the core layer, the polypropylene resin contained in each surface layer can contain a propylene copolymer (a copolymer of propylene and other monomers). As other monomers, for example, α-olefins such as ethylene, 1-butene, and 1-hexene can be listed. The propylene copolymer can specifically be a propylene-ethylene random copolymer, a propylene-ethylene block copolymer, a propylene-α-olefin copolymer, etc. From the viewpoint of improving heat resistance, each surface layer can contain a propylene-α-olefin copolymer.
[0063] From the viewpoint of improving heat resistance, the content of propylene monomer in the propylene copolymer can be set to 90 mol% or more, or 92 mol% or more based on the total monomers constituting the copolymer. From the viewpoint of imparting flexibility, the content of propylene monomer in the propylene copolymer can be set to 99.8 mol% or less, or 99.5 mol% or less based on the total monomers constituting the copolymer.
[0064] The hardness and complex elastic modulus of the core layer and each surface layer represent the hardness and complex elastic modulus measured by the nanoindentation method. The nanoindentation method refers to a measurement method for obtaining the mechanical properties of a sample by performing a quasi-static extrusion test on the measured object. The measuring device can use Hysitron TI-Premier (trade name) manufactured by Bruker Japan Co., Ltd., and the indenter can use a Berkovich-type diamond indenter manufactured by Bruker Japan Co., Ltd.
[0065] The measurement by the nanoindentation method was performed in a displacement control mode by extruding at an extrusion speed of 30 nm / sec to a depth of 30 nm, then maintaining the maximum depth for 1 second and then unloading at a speed of 30 nm / sec.
[0066] The measurement was performed by obtaining a shape image of the sample cross section using a shape measurement function of a measuring device that scans the sample surface with an indenter, and specifying 20 points at intervals of 1 μm or more on the target layer based on the shape image.
[0067] When calculating the hardness and complex elastic modulus, fused silica is tested as a standard sample in advance to calibrate the relationship between the contact depth and contact projection area between the indenter and the sample. Then, the unloading curve in the region of 60% to 95% of the maximum load during unloading is analyzed using the Oliver-Pharr method to calculate the hardness and complex elastic modulus.
[0068] The measurement using the nanoindentation method is to embed the substrate layer in the resin and then cut it to obtain a cross section, and then measure the cross section of the substrate layer. When embedded in the resin, in order to prevent the embedding resin and the substrate layer from peeling off, corona treatment can be applied to the front and back of the substrate layer as a surface treatment. In addition, the sample used in the measurement may not be in the state of only the substrate layer, but may also be in the state of a gas barrier film or a packaging film.
[0069] The hardness of the core layer is 0.07 GPa or more. The core layer with a hardness within this range is heat-resistant and can suppress the shrinkage of the substrate layer during heat sterilization. The hardness of the core layer can be 0.072 GPa or more, or 0.075 GPa or more. There is no particular upper limit on the hardness, but since the material uses a polypropylene resin, it can be set to 0.2 GPa or less.
[0070] The hardness of the first surface layer is in the range of 0.02 to 0.15 GPa. By making the hardness of the first surface layer above 0.02 GPa, it is possible to prevent the first surface layer from becoming too soft, thereby preventing decreased adhesion and decreased gas barrier properties. By making the hardness of the first surface layer below 0.15 GPa, it is possible to prevent the first surface layer from becoming too hard. As a result, the stress difference between the core layer and the gas barrier coating layer during heat sterilization is alleviated, and the gas barrier properties are not easily reduced. In addition, the adhesion strength between the core layer and the first surface layer is also not easily reduced. The hardness of the first surface layer can be 0.025 to 0.10 GPa, or 0.030 to 0.098 GPa.
[0071] The hardness of the second surface layer can be set to be the same as that of the first surface layer 11. This can improve not only the lamination strength with the adjacent layers but also the adhesion strength with the core layer.
[0072] In order to reduce the shrinkage of the substrate layer during heat sterilization and maintain the adhesion strength between the layers, the hardness of the core layer in the substrate layer is set to be the largest. That is, the hardness of the core layer is set to be greater than the hardness of the first surface layer, and the hardness of the core layer is set to be greater than the hardness of the second surface layer. The hardness of the first surface layer and the second surface layer can be the same or different.
[0073] The composite elastic modulus of the core layer can be more than 2.0GPa. The core layer with the composite elastic modulus within the range is heated and becomes stronger, so it is easier to suppress the shrinkage of the substrate layer during heat sterilization. The composite elastic modulus of the core layer can be more than 2.1GPa, or more than 2.13GPa. The upper limit of the composite elastic modulus is not particularly limited, but because the material uses polypropylene resin, it is below 4.5GPa.
[0074] The complex elastic modulus of the first surface layer can be in the range of 1.2 to 2.5 GPa. By making the complex elastic modulus of the first surface layer above 1.2 GPa, it is possible to prevent the first surface layer from becoming too soft, making it more difficult to produce decreased adhesion, decreased gas barrier properties, etc. By making the complex elastic modulus of the first surface layer below 2.5 GPa, it is possible to prevent the first surface layer from becoming too hard. As a result, the stress difference between the core layer and the gas barrier coating layer during heat sterilization becomes easier to ease, and the gas barrier properties are less likely to decrease. In addition, the adhesion strength between the core layer and the first surface layer is also less likely to decrease. The complex elastic modulus of the first surface layer can be 1.22 to 2.48 GPa, or 1.25 to 2.45 GPa.
[0075] The complex elastic modulus of the second skin layer can be set to be the same as that of the first skin layer. This can further improve not only the lamination strength with the adjacent layer but also the adhesion strength with the core layer.
[0076] In order to further reduce the shrinkage of the substrate layer during heat sterilization treatment and to easily maintain the adhesion strength between the layers, the composite elastic modulus of the core layer in the substrate layer can be set to be the largest. That is, the composite elastic modulus of the core layer can be set to be greater than the composite elastic modulus of the first surface layer, and the composite elastic modulus of the core layer can be set to be greater than the composite elastic modulus of the second surface layer. The composite elastic moduli of the first surface layer and the second surface layer can be the same or different.
[0077] The method for adjusting the hardness and complex elastic modulus of the core layer and each surface layer is not particularly limited. The hardness and complex elastic modulus of each layer containing a polypropylene resin can be adjusted by, for example, adjusting the type of resin constituting each layer, their mixing ratio when using multiple resins, the monomer ratio when using a copolymer, and the preparation method of each layer.
[0078] The thickness of each surface layer can be 0.1 μm or more. Thus, the surface layer can be evenly laminated on the core layer, and the deviation of the thickness of the surface layer can be suppressed. In addition, it is believed that the stress on the vapor-deposited layer during heat sterilization can be fully alleviated, and the deterioration of the gas barrier property can be suppressed. From this point of view, the thickness of each surface layer is, for example, 0.3 μm or more.
[0079] The upper limit of the thickness of each surface layer is not particularly limited, but from the viewpoint of more sufficiently ensuring the heat resistance of the entire base layer, it may be, for example, 2.0 μm or less, or 1.8 μm or less.
[0080] The ratio of the thickness of the first surface layer to the thickness of the core layer (thickness of the first surface layer / thickness of the core layer) can be 1 / 100 to 1 / 5, or 1 / 70 to 1 / 10. When the thickness ratio is within the above range, the heat resistance of the entire substrate layer can be more fully ensured, and the adhesion between the layers in the gas barrier film and the packaging film can be further improved.
[0081] The ratio of the thickness of the second surface layer to the thickness of the core layer (thickness of the second surface layer / thickness of the core layer) can be 1 / 100 to 1 / 5, or 1 / 70 to 1 / 10. When the thickness ratio is within the above range, the heat resistance of the entire substrate layer can be more fully ensured, and the adhesion between the layers in the gas barrier film and the packaging film can be further improved.
[0082] [Evaporated layer]
[0083] The vapor-deposited layer contains an inorganic oxide, and is a layer provided on the substrate layer from the viewpoint of improving the gas barrier properties to water vapor and oxygen, for example. The vapor-deposited layer may have transparency. Examples of the inorganic oxide include aluminum oxide, silicon oxide, tin oxide, magnesium oxide, or a mixture thereof. From the viewpoint of heat resistance during heat sterilization, at least one of aluminum oxide and silicon oxide may be used as the inorganic oxide.
[0084] The thickness of the vapor-deposited layer can be 5 to 300 nm. If the thickness of the vapor-deposited layer is 5 nm or more, it is easy to make the layer thickness uniform, and it is easier to ensure the function as a gas barrier film. In addition, if the thickness of the vapor-deposited layer is 300 nm or less, it is easy to give flexibility to the vapor-deposited layer, and even if external factors such as bending or stretching are applied after the layer is formed, the vapor-deposited layer is not easy to crack. From this point of view, the thickness of the vapor-deposited layer is, for example, 6 nm or more, 150 nm or less, or 100 nm or less. The thickness of the vapor-deposited layer can be 5 to 80 nm, or 20 to 40 nm.
[0085] The deposited layer 2 can be formed by a conventional vacuum deposition method. In addition, sputtering, ion plating, plasma vapor deposition (CVD), etc., which are other thin film forming methods, can also be used. However, if productivity is taken into consideration, the vacuum deposition method is currently superior.
[0086] As the heating means of the vacuum evaporation method, any one of electron beam heating, resistance heating, and induction heating can be used. Considering the wide range of evaporation material selectivity, electron beam heating can be used as the heating means.
[0087] In order to improve the adhesion between the vapor-deposited layer and the substrate layer and the compactness of the vapor-deposited layer, a plasma-assisted method or an ion-beam-assisted method can also be used to form the vapor-deposited layer. In addition, in order to improve the transparency of the vapor-deposited layer, reactive vapor deposition in which various gases such as oxygen are blown into the vapor deposition can also be used.
[0088] [Adhesion-promoting coating]
[0089] An anchor coating layer may be further provided between the substrate layer and the vapor-deposited layer, thereby further improving the adhesion and gas barrier properties of the two layers after heat sterilization.
[0090] Examples of coating agents for providing the anchor coating layer include acrylic resins, epoxy resins, acrylic urethane resins, polyester urethane resins, polyether urethane resins, etc. From the viewpoint of heat resistance and interlayer adhesion strength, acrylic urethane resins and polyester urethane resins may also be used as coating agents.
[0091] The thickness of the adhesion coating layer can be 0.05 to 2 μm. If the thickness of the adhesion coating layer is 0.05 μm or more, the adhesion between the substrate layer and the vapor-deposited layer can be further improved. In addition, if the thickness of the adhesion coating layer is 2 μm or less, it is easy to give flexibility to the adhesion coating layer, and it is easy to maintain the gas barrier properties even if external factors such as bending or stretching are applied after the layer is formed. From this point of view, the thickness of the adhesion coating layer is, for example, 0.08 μm or more, and can also be 1 μm or less.
[0092] [Gas barrier coating layer]
[0093] The purpose of providing the gas barrier coating layer is to protect the vapor deposited layer and to supplement the gas barrier property. The gas barrier coating layer can be formed by a cured product of a composition containing: a water-soluble polymer having a hydroxyl group and at least one selected from metal alkoxides, silane coupling agents and their hydrolyzates.
[0094] Examples of the water-soluble polymer having a hydroxyl group include polyvinyl alcohol, polyvinyl pyrrolidone, starch, methyl cellulose, carboxymethyl cellulose, sodium alginate, etc. In particular, when polyvinyl alcohol (PVA) is used as a coating agent, the gas barrier properties tend to be more excellent.
[0095] Examples of the metal alkoxide include compounds represented by the following general formula.
[0096] M(OR 1 ) m (R 2 ) n-m
[0097] In the above formula, R 1 It is a monovalent organic group having 1 to 8 carbon atoms, and may be an alkyl group such as methyl or ethyl. 1 is a hydrolyzable group). 2 is a monovalent organic group having 1 to 8 carbon atoms, and may be an alkyl group such as methyl or ethyl. M represents an n-valent metal atom such as Si, Ti, Al, or Zr. m is an integer from 1 to n. 1 and R 2 In the case of R 1 Each other or R 2 They can be the same or different from each other.
[0098] Specific examples of metal alkoxides include tetraethoxysilane [Si(OC 2 H 5 ) 4 〕、Triisopropoxyaluminum〔Al(O-2'-C 3 H 7 ) 3 After hydrolysis, tetraethoxysilane (TEOS) and triisopropoxyaluminum tend to be relatively stable in aqueous solvents.
[0099] Examples of the silane coupling agent include compounds represented by the following general formula.
[0100] Si(OR 21 ) p (R 22 ) 3-p R 23 (2)
[0101] In the above formula, R 21 represents an alkyl group such as methyl or ethyl, R 22 represents a monovalent organic group such as an alkyl group, an aralkyl group, an aryl group, an alkenyl group, an alkyl group substituted by an acryloyloxy group, or an alkyl group substituted by a methacryloyloxy group, and R 23 represents a monovalent organic functional group, and p represents an integer of 1 to 3. 21 or R 22 When there are multiple 21 Each other or R 22 They may be the same or different from each other. 23The monovalent organic functional group represented by may include a glycidyloxy group, an epoxy group, a mercapto group, a hydroxyl group, an amino group, an alkyl group substituted with a halogen atom, or an isocyanate group. Compounds in which the above-mentioned silane coupling agent is in the form of a multimer such as a dimer or trimer may also be used.
[0102] Specific examples of the silane coupling agent include vinyltrimethoxysilane, γ-chloropropylmethyldimethoxysilane, γ-chloropropyltrimethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropylmethyltriethoxysilane, γ-methacryloxypropyltrimethoxysilane, γ-methacryloxypropylmethyldimethoxysilane, and 1,3,5-tris(3-methoxysilylpropyl)isocyanurate.
[0103] The gas barrier coating layer can be formed by coating the gas barrier coating layer forming composition on the above-mentioned vapor deposition layer and then heating and drying. The gas barrier coating layer forming composition can be prepared as follows: a water-soluble polymer is dissolved in an aqueous solvent (water, a water / alcohol mixed solvent, etc.), and at least one of a metal alkoxide and a silane coupling agent is mixed in the obtained substance, or a substance obtained by pre-hydrolyzing them is mixed. In the range that does not impair the gas barrier properties, an isocyanate compound, or a known additive such as a dispersant, a stabilizer, a viscosity modifier, a colorant, etc. can also be added to the composition (mixed solution) as needed.
[0104] When PVA is used as a water-soluble polymer, the amount of PVA in the composition can be 20 to 70% by mass, or 25 to 60% by mass, based on the total solid content of the composition. When the amount of PVA is 20% by mass or more, the softness of the layer can be maintained, and a gas barrier coating layer can be easily formed. On the other hand, when the amount of PVA is 70% by mass or less, it is easy to give a more sufficient gas barrier property to the gas barrier film.
[0105] When TEOS is used as the metal alkoxide, the amount of TEOS in the composition can be 30 to 80% by mass, or 40 to 75% by mass, based on the total solid content of the composition. When the amount of TEOS is 30% by mass or more, high gas barrier properties are easily exhibited. On the other hand, when the amount of TEOS is 80% by mass or less, the flexibility of the layer is easily maintained. The amount of TEOS is converted into SiO 2 Calculated.
[0106] When isocyanurate silane is used as a silane coupling agent, the mass ratio may be 1 to 20% by mass, or 5 to 15% by mass, based on the total solid content of the composition. When the amount of isocyanurate silane is 1% by mass or more, hot water resistance is easily obtained, and the adhesion strength is not easily reduced. On the other hand, when the amount of isocyanurate silane is 20% by mass or less, the amount of other components in the composition does not become too low, and as a result, high gas barrier properties are easily obtained.
[0107] The thickness of the gas barrier coating layer may be 0.1 to 5 μm. If the thickness of the gas barrier coating layer is 0.1 μm or more, high gas barrier properties are easily exhibited. In addition, if the thickness of the gas barrier coating layer is 5 μm or less, from the viewpoint of suppressing the reduction of gas barrier properties caused by cracks in the layer during coating, the thickness of the gas barrier coating layer is, for example, 0.2 μm or more, and may be 1 μm or less.
[0108] <Packaging film>
[0109] Figure 3 It is a schematic cross-sectional view showing the packaging film according to the first embodiment. Figure 3 The packaging film 20 shown has a structure in which a sealant layer 23 is laminated on a gas barrier coating layer 3 of a gas barrier film 10a via an adhesive layer 24 .
[0110] Figure 4 It is a schematic cross-sectional view showing a packaging film according to a modified example of the first embodiment. Figure 4 In the packaging film 30 shown, a sealant layer 23 is laminated on the second surface layer 13 of the gas barrier film 10b via an adhesive layer 24, and an outer layer film (outermost layer) 22 is laminated on the gas barrier coating layer 3 of the gas barrier film 10b via a second adhesive layer 25. Figure 4 In the packaging film 30 shown, the direction of the gas barrier film 10b may be reversed. That is, the outer layer film (second substrate layer) 22 may be laminated on the second surface layer 13 of the gas barrier film 10b via the second adhesive layer 25, and the sealing layer 23 may be laminated on the gas barrier coating layer 3 of the gas barrier film 10b via the adhesive layer 24.
[0111] (Outer membrane)
[0112] The outer film is a layer provided for the purpose of improving the rigidity of the packaging bag. Therefore, the outer film can be called the second substrate layer. In order to use the packaging film as a single-material packaging material, the outer film contains a polyolefin resin. Examples of polyolefin resins include polyethylene and polypropylene, but polypropylene can be used from the viewpoint of resistance to retort treatment. Here, the polypropylene can be a homopolymer polypropylene or a propylene copolymer, but homopolymer polypropylene can be used from the viewpoint of heat resistance.
[0113] The outer layer film may be a stretched film or an unstretched film, but may be a stretched film from the viewpoint of oxygen barrier properties.
[0114] The thickness of the outer layer film is not particularly limited, and can be set to, for example, 15 to 200 μm.
[0115] (Sealing layer)
[0116] The sealing layer contains a polyolefin resin. Specifically, as the polyolefin resin, low-density polyethylene resin (LDPE), medium-density polyethylene resin (MDPE), linear low-density polyethylene resin (LLDPE), ethylene-vinyl acetate copolymer (EVA), ethylene-α-olefin copolymer, ethylene-(meth)acrylic acid copolymer and other ethylene resins, homopolymerized polypropylene resin (PP), propylene-ethylene random copolymer, propylene-ethylene block copolymer, propylene-α-olefin copolymer and other polypropylene resins, or mixtures thereof can be used. The material of the sealing layer can be appropriately selected from the above-mentioned thermoplastic resins according to the use and the temperature conditions of boiling treatment, steaming treatment, etc.
[0117] The sealing layer and the substrate layer may be a polyolefin film. The sealing layer may be, for example, a resin layer having a single-layer structure and having polypropylene as a main material, but is not limited thereto. The sealing layer may contain a polypropylene film or may be composed of a polypropylene film.
[0118] The thermoplastic resin constituting the sealing layer may be stretched or unstretched. From the viewpoint of lowering the melting point and facilitating heat sealing, it may be unstretched. From the viewpoint of improving the sealing property of heat sealing, the polypropylene film constituting the sealing layer may be an unstretched polypropylene film.
[0119] The thickness of the sealing layer is not particularly limited, and may be, for example, 15 to 200 μm.
[0120] (Adhesive layer)
[0121] The adhesive layer is a layer that bonds the films together. As the adhesive constituting the adhesive layer, for example, polyurethane resins formed by reacting difunctional or higher-functional isocyanate compounds with main agents such as polyester polyols, polyether polyols, acrylic polyols, and carbonate polyols can be cited. Various polyols can be used alone or in combination of two or more. From the viewpoint of heat resistance (resistance to retort treatment) during heat sterilization, two-component curing type urethane adhesives can also be used.
[0122] In order to promote adhesion, the polyurethane resin may be mixed with carbodiimide compounds, oxazoline compounds, epoxy compounds, phosphorus compounds, silane coupling agents, etc. From the perspective of environmental protection, as an adhesive, an adhesive whose polymer component is derived from biomass or an adhesive with biodegradability may also be used. In addition, the adhesive may also be an adhesive with barrier properties.
[0123] From the viewpoint of obtaining the desired bonding strength, followability, and processability, the coating amount of the adhesive may be, for example, 0.5 to 10 g / m 2 .
[0124] The thickness of the adhesive layer is, for example, 0.5 μm to 10 μm. When the thickness of the adhesive layer is 0.5 μm or more, the peeling of the gas barrier coating layer and the sealing layer can be well suppressed. When the thickness of the adhesive layer is 10 μm or less, the packaging film can be easily made of a single material (details will be described later). The thickness of the adhesive layer can be 1 μm or more, 2 μm or more, 8 μm or less, 6 μm or less, or 5 μm or less.
[0125] (Second Adhesive Layer)
[0126] The second adhesive layer is a layered component that bonds the gas barrier film and the outer film. The material of the adhesive contained in the second adhesive layer is the same as the material of the adhesive contained in the adhesive layer. Therefore, the description of the material contained in the second adhesive layer is omitted. The thickness of the second adhesive layer is the same as the thickness of the adhesive layer, for example, 0.5μm to 10μm.
[0127] (Polyolefin content)
[0128] The total mass ratio of the polyolefin (in this embodiment, polypropylene) in the packaging film is 90 mass % or more. Therefore, the packaging film can be said to be a packaging material composed of a single raw material (single material) and has excellent recyclability. From the viewpoint of further improving recyclability, the polyolefin content in the packaging film may be 92.5 mass % or more, or 95 mass % or more based on the total amount of the packaging film.
[0129] (Thermal shrinkage of substrate layer)
[0130] After the substrate layer is exposed to 120°C for 15 minutes (hereinafter referred to as "after heating"), the heat shrinkage of the substrate layer in the MD direction calculated by the following formula (1) is 1% or more. For example, after the substrate layer or the gas barrier film containing the substrate layer is heated in an oven at 120°C for 15 minutes, the heat shrinkage of the substrate layer in the MD direction calculated by the following formula (1) is 1% or more. From the viewpoints of reducing deformation during bag making and inhibiting peeling between the gas barrier film and the sealing layer, the above-mentioned heat shrinkage in the MD direction is, for example, less than 12%, less than 11%, less than 10%, less than 9%, less than 8% or less than 7%. In addition, for example, the above-mentioned heat shrinkage of the twin-screw stretched polypropylene film is more than 1%, while the above-mentioned heat shrinkage of the PET film is less than 1%.
[0131] Heat shrinkage in MD direction (%) = (MD direction length before heating - MD direction length after heating) / MD direction length before heating × 100 (1)
[0132] After the above heating, the heat shrinkage rate of the substrate layer in the TD direction obtained by the following formula (2) is not particularly limited, and is, for example, 1% or more. From the viewpoint of reducing deformation during bag making and inhibiting peeling between the gas barrier film and the sealant layer, the above heat shrinkage rate in the TD direction is, for example, 12% or less, 11% or less, 10% or less, 9% or less, 8% or less, or 7% or less.
[0133] Thermal shrinkage in TD direction (%) = (TD direction length before heating - TD direction length after heating) / TD direction length before heating × 100 (2)
[0134] (Hardness of adhesive layer)
[0135] Based on the heat shrinkage of the substrate layer, in this embodiment, after the packaging film is subjected to a retort treatment, the hardness of the adhesive layer is greater than 0.1 MPa and less than 0.9 MPa. In this case, the adhesive layer can well follow the expansion and contraction of the substrate layer accompanied by a heat treatment such as a retort treatment and a boiling treatment. Therefore, even if the packaging film including the substrate layer having the above-mentioned heat shrinkage is subjected to the above-mentioned heat treatment, it is not easy to peel off between the gas barrier film and the sealing layer. In addition, the generation of cracks in the adhesive layer during cooling after the above-mentioned heat treatment, and the generation of damage to the gas barrier film (at least one of the vapor-deposited layer and the gas barrier coating layer) accompanying the generation of the cracks are suppressed. The hardness of the adhesive layer before the retort treatment is not particularly limited, but is, for example, greater than 1.0 MPa.
[0136] The hardness of the adhesive layer can be controlled by the material of the adhesive, the amount of curing agent, the aging time, etc. The narrower the distance between the molecular chains of the adhesive, the harder the adhesive layer tends to be. The more voluminous the adhesive is, the softer the adhesive layer tends to be. The hardness of aliphatic adhesive layers tends to be harder than that of alicyclic or aromatic adhesive layers. The hardness of alicyclic adhesive layers tends to be harder than that of aromatic adhesive layers. The more curing agent is contained in the adhesive layer, the harder the adhesive layer tends to be. The longer the aging time, the harder the adhesive layer tends to be.
[0137] The hardness of the adhesive layer in the packaging film can be obtained by measuring the hardness of the portion exposed from the sealing layer (exposed portion). The removal of the sealing layer to expose the adhesive layer can be implemented, for example, using an oblique cutting device. In the present embodiment, the hardness of the adhesive layer can be measured and obtained by a nanoindentation method. The hardness of a sample such as an adhesive layer is calculated, for example, by the following method. First, fused quartz is preliminarily tested as a standard sample, and the relationship between the contact depth and the contact projection area between the indenter and the sample is calibrated. Thereafter, the hardness of the sample is calculated by analyzing the unloading curve in the region of 20 to 95% relative to the maximum load during unloading using the Oliver-Pharr method.
[0138] (Hardness of outer film)
[0139] After the outer layer film is exposed to 120° C. for 15 minutes, the heat shrinkage rate of the outer layer film in the MD direction obtained by the above formula (1) is 1% or more. For example, after the outer layer film or the laminate of the outer layer film and the gas barrier film 10b is heated in an oven at 120° C. for 15 minutes, the heat shrinkage rate of the outer layer film in the MD direction obtained by the following formula (1) is 1% or more. The following heat shrinkage rate in the MD direction is, for example, 12% or less, 11% or less, 10% or less, 9% or less, 8% or less, or 7% or less.
[0140] The heat shrinkage rate in the TD direction of the outer layer film after the heating as determined by the above formula (2) is not particularly limited, and is, for example, 1% to 12%.
[0141] (Hardness of the second adhesive layer)
[0142] In this modification, after the packaging film is subjected to a retort treatment, the hardness of the second adhesive layer is greater than 0.1 MPa and less than 0.9 MPa. In this case, the second adhesive layer can well follow the expansion and contraction of the outer film caused by a heat treatment such as a retort treatment or a boiling treatment. Therefore, even if the packaging film containing the second adhesive layer having the above-mentioned heat shrinkage rate is subjected to the above-mentioned heat treatment, it is not easy for the gas barrier film and the outer film to peel off. Moreover, the occurrence of cracks in the second adhesive layer during cooling after the above-mentioned heat treatment, and the occurrence of damage to the gas barrier film (at least one of the vapor-deposited layer and the gas barrier coating layer) accompanying the occurrence of the cracks can be suppressed. The hardness of the second adhesive layer before the retort treatment is not particularly limited, and is, for example, greater than 1.0 MPa.
[0143] The hardness of the second adhesive layer can be controlled by the material of the adhesive, the amount of curing agent, the aging time, etc. The narrower the distance between the molecular chains of the adhesive, the harder the second adhesive layer tends to be. The more voluminous the adhesive is, the softer the second adhesive layer tends to be. The hardness of the aliphatic second adhesive layer tends to be harder than that of the alicyclic or aromatic second adhesive layer. The hardness of the alicyclic second adhesive layer tends to be harder than that of the aromatic second adhesive layer. The more the amount of curing agent contained in the second adhesive layer, the harder the second adhesive layer tends to be. The longer the aging time, the harder the second adhesive layer tends to be.
[0144] <Packaging bag>
[0145] The packaging bag is obtained by making the above packaging film into a bag. The packaging bag can contain contents such as food and medicine.
[0146] The packaging bag may be a packaging bag formed by folding a piece of packaging film in half so that the sealing layers are opposite to each other and then heat-sealing in three directions, or may be a packaging bag formed by overlapping two pieces of packaging materials so that the sealing layers are opposite to each other and then heat-sealing in four directions. In addition, the packaging bag may be a shape having a curved portion (bent portion) such as a self-supporting bag. The packaging bag of this embodiment can maintain high gas barrier properties even if it has a curved portion.
[0147] [Second embodiment]
[0148] <Laminate>
[0149] Figure 5 (a) is a schematic top view of a laminated body according to one embodiment, Figure 5 (b) is a schematic cross-sectional view showing a laminated body according to one embodiment. Figure 5The laminate 35 shown in (a) and (b) is a sheet-like member (gas barrier laminate) having gas barrier properties, and is, for example, a sheet-like packaging material used for manufacturing packaging bags, etc. The laminate 35 can be suitably used for, for example, heat treatment such as retorting treatment or boiling treatment. The laminate 35 can also correspond to the packaging film of the first embodiment.
[0150] Retort treatment is generally a method of sterilizing molds, yeasts, bacteria and other microorganisms under pressure in order to preserve food, medicines, etc. Usually, the packaging bag containing food is sterilized under pressure for 10 to 120 minutes at 105 to 140°C and 0.15 to 0.30 MPa. Retort devices include steam type using heated steam and hot water type using pressurized heated water, which are appropriately distinguished and used according to the sterilization conditions of the food, etc. as the content. Boiling treatment is a method of wet heat sterilization for preserving food, medicines, etc. Although it also depends on the content, it is usually treated with wet heat sterilization for 10 to 120 minutes at 60 to 100°C and atmospheric pressure for packaging bags containing food, etc. Boiling treatment is usually carried out using a hot water tank at a temperature below 100°C. As a method, there is an intermittent method in which the bag is immersed in a hot water tank at a certain temperature and taken out after treatment for a certain period of time, and a continuous method in which the bag is treated by tunneling through the hot water tank.
[0151] The laminate 35 includes a barrier layer 40, a sealing layer 50, and an adhesive layer 60. The barrier layer 40 and the sealing layer 50 are stacked on each other and bonded by the adhesive layer 60. In the laminate 35, the barrier layer 40, the adhesive layer 60, and the sealing layer 50 are stacked in this order. Figure 5 As shown in (a), direction MD is the flow direction (long side direction) of the laminate 35, and direction TD is the width direction (short side direction) of the laminate 35. In addition, the direction orthogonal to both directions MD and TD is the stacking direction of the components included in the laminate 35.
[0152] [Barrier layer 40]
[0153] The barrier layer 40 is a member that functions as a support in the laminate 35 and exhibits gas barrier properties against gases such as water vapor and oxygen. The barrier layer 40 may also correspond to the gas barrier film of the first embodiment. Figure 5 As shown, the barrier layer 40 includes a substrate 41, a bonding layer 42, a vapor-deposited layer 43, and a barrier coating layer 44. In the barrier layer 40, the substrate 41, the bonding layer 42, the vapor-deposited layer 43, and the barrier coating layer 44 are stacked in sequence. Therefore, the bonding layer 42 and the vapor-deposited layer 43 are located between the substrate 41 and the barrier coating layer 44 in the stacking direction, and the bonding layer 42 is located between the substrate 41 and the vapor-deposited layer 43. In this embodiment, the barrier coating layer 44 in the barrier layer 40 is closest to the adhesive layer 60 in the stacking direction. Therefore, the substrate 41 in the barrier layer 40 is farthest from the adhesive layer 60 in the stacking direction.
[0154] [Base material 41]
[0155] The substrate 41 is a plastic member (substrate layer) that functions as the outermost layer of the laminate 35. The thickness of the substrate 41 is not particularly limited. The thickness can be set to 6 to 200 μm depending on the application, but from the viewpoint of material reduction for reducing environmental load and obtaining excellent heat resistance, impact resistance, and excellent gas barrier properties, it can be 9 to 50 μm, 12 to 38 μm, or 18 to 30 μm.
[0156] From the viewpoint of the recycling adaptability of the laminate 35, the substrate 41 is, for example, a polyolefin film. In the present embodiment, the substrate 41 may contain a polypropylene film or may be composed of a polypropylene film. The polypropylene film may also be an acid-modified polypropylene film obtained by graft-modifying polypropylene using an unsaturated carboxylic acid, an anhydride of an unsaturated carboxylic acid, an ester of an unsaturated carboxylic acid, or the like. In addition, as the polypropylene, a polypropylene resin such as a homopolymer polypropylene resin (PP), a propylene-ethylene random copolymer, a propylene-ethylene block copolymer, a propylene-α-olefin copolymer, or the like may be used.
[0157] Various additives such as a flame retardant, a slip agent, an anti-blocking agent, an antioxidant, a light stabilizer, a thickener, and an antistatic agent may be added to the polypropylene film constituting the base material 41 .
[0158] The polypropylene film constituting the substrate 41 may be a stretched film or an unstretched film. However, from the viewpoints of impact resistance, heat resistance, water resistance, dimensional stability, etc., the polypropylene film may be a stretched polypropylene film. Thus, the thermal fusion bonding of the substrate 41 can be suppressed in the heat sealing process during bag making. In addition, in the application of heat treatment such as retorting treatment and boiling treatment, the laminate 35 can be more preferably used. There is no particular limitation on the stretching method, and any method can be used as long as it can provide a dimensionally stable film, such as stretching by blow molding, single-screw stretching, twin-screw stretching, etc.
[0159] On the substrate 41, on its laminated surface, various pretreatments such as corona treatment, plasma treatment, flame treatment, etc. may be performed within a range that does not impair the barrier performance, or a coating such as an easy-adhesion layer may be provided.
[0160] [Sealing layer]
[0161] The adhesion layer 42 functions as a layer (adhesion-enhancing coating) capable of improving the adhesion performance of the vapor-deposited layer 43 on the substrate 41, and is provided directly above the substrate 41. Therefore, the adhesion layer 42 is located between the substrate 41 and the vapor-deposited layer 43. By providing the adhesion layer 42, the smoothness of the surface on which the vapor-deposited layer 43 is provided on the barrier layer 40 can be improved. In addition, by improving the smoothness, it becomes easy to form the vapor-deposited layer 43 without defects and uniformly, and it is easy to exhibit high barrier properties. The adhesion layer 42 can be formed, for example, using an adhesion-enhancing coating agent.
[0162] Examples of the adhesion promoter include polyester polyurethane resins and polyether polyurethane resins. From the viewpoint of heat resistance and interlayer adhesive strength, polyester polyurethane resins can be used as the adhesion promoter.
[0163] The thickness of the adhesive layer 42 is not particularly limited, and may be in the range of 0.01 to 5 μm, 0.03 to 3 μm, or 0.05 to 2 μm. If the thickness of the adhesive layer 42 is above the lower limit, there is a tendency to obtain a more sufficient interlayer bonding strength, while if it is below the upper limit, there is a tendency to easily exhibit the desired gas barrier properties.
[0164] As a method for coating the adhesion layer 42 on the substrate 41, a known coating method can be used without particular limitation, and examples thereof include a dipping method (immersion method); a method using a sprayer, a coater, a printer, a brush, etc. In addition, as the types of coaters and printers used in the above methods and their coating methods, examples thereof include gravure coaters such as direct gravure method, reverse gravure method, contact reverse gravure method, offset gravure method, reverse roll coaters, micro gravure coaters, chamber blade combined coaters, air knife coaters, dip coaters, rod coaters, comma coaters, die coaters, etc.
[0165] The coating amount of the adhesion layer 42 is 1 m after the adhesion promoter coating agent is applied and dried. 2 The mass can be 0.01~5g / m 2 , can also be 0.03~3g / m 2 . After applying the adhesion promoter and drying, every 1m 2 When the mass is not less than the above lower limit, film formation tends to be sufficient, while on the other hand, when it is not more than the above upper limit, sufficient drying tends to be easy and the solvent tends to be less likely to remain.
[0166] The method of drying the adhesion layer 42 is not particularly limited, and examples thereof include a natural drying method, a drying method in an oven set to a predetermined temperature, a method using a dryer with the above-mentioned coating machine, such as an arch dryer, a suspension dryer, a drum dryer, an infrared dryer, etc. Furthermore, the drying conditions can be appropriately selected according to the drying method, and for example, in the method of drying in an oven, drying can be performed at a temperature of 60 to 100° C. for about 1 second to 2 minutes.
[0167] A polyvinyl alcohol resin may be used instead of the polyurethane resin as the adhesion layer 42. The polyvinyl alcohol resin may be any resin having a vinyl alcohol unit obtained by saponifying a vinyl ester unit, and examples thereof include polyvinyl alcohol (PVA) and ethylene-vinyl alcohol copolymer (EVOH).
[0168] As PVA, for example, there can be cited resins obtained by polymerizing vinyl esters such as vinyl acetate, vinyl formate, vinyl propionate, vinyl valerate, vinyl caprate, vinyl laurate, vinyl stearate, vinyl pivalate, and vinyl versatate, and then saponifying them. PVA can be a copolymer-modified or post-modified modified PVA. Modified PVA is obtained, for example, by copolymerizing vinyl esters and unsaturated monomers copolymerizable with vinyl esters and then saponifying them. Examples of the unsaturated monomer copolymerizable with vinyl esters include olefins such as ethylene, propylene, isobutylene, α-octene, α-dodecene, and α-octadecene; hydroxyl-containing α-olefins such as 3-butene-1-ol, 4-pentene-1-ol, and 5-hexene-1-ol; unsaturated acids such as acrylic acid, methacrylic acid, crotonic acid, maleic acid, maleic anhydride, itaconic acid, and undecylenic acid; nitriles such as acrylonitrile and methacrylonitrile; amides such as diacetone acrylamide, acrylamide, and methacrylamide; olefin sulfonic acids such as vinyl sulfonic acid, allyl sulfonic acid, and methyl allyl sulfonic acid; vinyl compounds such as alkyl vinyl ether, dimethyl allyl vinyl ketone, N-vinyl pyrrolidone, vinyl chloride, vinyl ethylene carbonate, 2,2-dialkyl-4-vinyl-1,3-dioxolane, glycerol monoallyl ether, and 3,4-diacetoxy-1-butene; vinylidene chloride, 1,4-diacetoxy-2-butene, and vinyl carbonate.
[0169] The degree of polymerization of PVA is, for example, 300 to 3000. When the degree of polymerization is less than 300, the barrier properties are likely to decrease. When it exceeds 3000, the viscosity is too high and the coating adaptability is likely to decrease. The saponification degree of PVA can be 90 mol% or more, 95 mol% or more, or 99 mol% or more. In addition, the saponification degree of PVA can be 100 mol% or less, or 99.9 mol% or less. The degree of polymerization and saponification of PVA can be measured according to the method described in JIS K 6726 (1994).
[0170] EVOH is generally obtained by saponifying a copolymer of ethylene and a vinyl ester of an acid such as vinyl acetate, vinyl formate, vinyl propionate, vinyl valerate, vinyl caprate, vinyl laurate, vinyl stearate, vinyl pivalate, or vinyl versatate.
[0171] The degree of polymerization of EVOH is, for example, 300 to 3000. When the degree of polymerization is less than 300, the barrier properties are likely to decrease. When it exceeds 3000, the viscosity is too high and the coating adaptability is likely to decrease. The saponification degree of the vinyl ester component of EVOH can be 90 mol% or more, 95 mol% or more, or 99 mol% or more. In addition, the saponification degree of EVOH can be 100 mol% or less, or 99.9 mol% or less. The saponification degree of EVOH is determined by performing nuclear magnetic resonance (NMR). 1 H-NMR) measurement, and determined from the peak area of hydrogen atoms contained in the vinyl ester structure and the peak area of hydrogen atoms contained in the vinyl alcohol structure.
[0172] The ethylene unit content of EVOH is, for example, 10 mol% or more, 15 mol% or more, 20 mol% or more, or 25 mol% or more. In addition, the ethylene unit content of EVOH may be 65 mol% or less, 55 mol% or less, or 50 mol% or less. If the ethylene unit content is 10 mol% or more, the gas barrier properties or dimensional stability under high humidity can be well maintained. On the other hand, if the ethylene unit content is 65 mol% or less, the gas barrier properties can be improved. The ethylene unit content of EVOH can be obtained by the NMR method.
[0173] When a polyvinyl alcohol-based resin is used as the adhesion layer 42 , examples of a method for forming the adhesion layer 42 include coating using a polyvinyl alcohol-based resin solution and multilayer extrusion.
[0174] [Evaporated layer 43]
[0175] The vapor-deposited layer 43 is a layer (gas barrier layer) that shows gas barrier properties to water vapor and oxygen, and contains at least one of a metal and an inorganic oxide. The vapor-deposited layer 43 is arranged directly above the adhesion layer 42. The vapor-deposited layer 43 can be a single-layer structure or a laminated structure. Therefore, the vapor-deposited layer 43 contains at least one of a metal vapor-deposited layer and an inorganic oxide layer. In the case where the vapor-deposited layer 43 has a metal vapor-deposited layer, aluminum, stainless steel, etc. can be listed as metals contained in the metal vapor-deposited layer. In the case where the vapor-deposited layer 43 has an inorganic oxide layer, aluminum oxide, silicon oxide, magnesium oxide, tin oxide, etc. can be listed as inorganic oxides contained in the inorganic oxide layer. From the viewpoint of transparency and barrier properties, as an inorganic oxide, it can be selected from the group consisting of aluminum oxide, silicon oxide and magnesium oxide. In addition, from the viewpoint of excellent tensile elongation during processing, the inorganic oxide layer can also be set as a layer using silicon oxide. By using an inorganic oxide layer, high barrier properties can be obtained with an extremely thin layer within the range that does not affect the recyclability of the stack 35.
[0176] In the case where the vapor-deposited layer 43 is an inorganic oxide layer using silicon oxide, the O / Si ratio of the inorganic oxide layer is preferably greater than 1.7. If the O / Si ratio is greater than 1.7, the content ratio of metal Si is suppressed, and good transparency is easily obtained. In addition, the O / Si ratio may be less than 2.0. If the O / Si ratio is less than 2.0, the crystallinity of SiO becomes higher, which can prevent the inorganic oxide layer from becoming too hard and obtain good tensile resistance. Thus, it is possible to suppress the generation of cracks in the inorganic oxide layer when the barrier coating 44 is stacked. In addition, after being formed into a packaging bag, the substrate 41 sometimes shrinks due to the heat during boiling or steaming, but when the O / Si ratio is less than 2.0, the inorganic oxide layer easily follows the above shrinkage, which can suppress the reduction of barrier properties. From the viewpoint of more fully obtaining the above effect, the O / Si ratio of the inorganic oxide layer can be 1.75 to 1.9, or 1.8 to 1.85.
[0177] In the case where the deposited layer 43 is an inorganic oxide layer using silicon oxide, the O / Si ratio of the inorganic oxide layer can be obtained by X-ray photoelectron spectroscopy (XPS). For example, the measuring device can use an X-ray photoelectron spectrometer (manufactured by JEOL Ltd., trade name: JPS-90MXV), the X-ray source uses non-monochromatized MgKα (1253.6 eV), and the measurement is performed with an X-ray output of 100 W (10 kV-10 mA). In order to obtain the quantitative analysis of the O / Si ratio, relative sensitivity factors of 2.28 for O1s and 0.9 for Si2p can be used respectively.
[0178] The thickness of the vapor-deposited layer 43 is, for example, 5 nm to 80 nm. When the thickness of the vapor-deposited layer 43 is 5 nm or more, sufficient water vapor barrier properties can be obtained. In addition, when the thickness of the vapor-deposited layer 43 is 80 nm or less, the deformation caused by the internal stress of the film can be suppressed to generate cracks, thereby suppressing the decrease in water vapor barrier properties. In addition, when the thickness of the vapor-deposited layer 43 exceeds 80 nm, the cost is likely to increase due to the increase in the amount of material used and the lengthening of the film formation time, so it is not preferred from an economic point of view. From the same point of view as above, the thickness of the vapor-deposited layer 43 can also be 20 nm to 40 nm.
[0179] The vapor deposition layer 43 can be formed by vacuum film formation, for example. In vacuum film formation, a physical vapor phase growth method or a chemical vapor phase growth method can be used. As the physical vapor phase growth method, vacuum vapor deposition method, sputtering method, ion plating method, etc. can be listed, but it is not limited to them. As the chemical vapor phase growth method, thermal CVD method, plasma CVD method, optical CVD method, etc. can be listed, but it is not limited to them.
[0180] In the above-mentioned vacuum film formation, resistance heating vacuum evaporation method, EB (Electron Beam) heating vacuum evaporation method, induction heating vacuum evaporation method, sputtering method, reactive sputtering method, dual magnetron sputtering method, plasma chemical vapor growth method (PECVD method) and the like can also be used. However, considering productivity, vacuum evaporation method may be the best at present. As a heating means for vacuum evaporation method, any one of electron beam heating method, resistance heating method and induction heating method can be used.
[0181] [Barrier coating 44]
[0182] The barrier coating layer 44 is a gas barrier coating layer (gas barrier coating layer) and is provided on the substrate 41. The barrier coating layer 44 is, for example, a layer formed using a gas barrier coating layer forming composition (hereinafter also referred to as a coating agent) containing at least one selected from a hydroxyl-containing polymer compound, a metal alkoxide, a silane coupling agent, and a hydrolyzate thereof.
[0183] From the viewpoint of more fully maintaining the gas barrier properties after hot water treatment such as retorting treatment, the coating agent may contain at least a silane coupling agent or its hydrolyzate, or may contain at least one selected from a hydroxyl-containing polymer compound, a metal alkoxide and their hydrolyzates, and a silane coupling agent or its hydrolyzate, or may contain a hydroxyl-containing polymer compound or its hydrolyzate, a metal alkoxide or its hydrolyzate, and a silane coupling agent or its hydrolyzate. The coating agent may be prepared, for example, by mixing a metal alkoxide and a silane coupling agent directly or after a treatment such as pre-hydrolysis in a solution in which a hydroxyl-containing polymer compound as a water-soluble polymer is dissolved in an aqueous (water or water / alcohol mixed) solvent.
[0184] The components contained in the coating agent for forming the barrier coating 44 are described in detail. Examples of the hydroxyl-containing polymer compound used in the coating agent include polyvinyl alcohol, polyvinyl pyrrolidone, starch, methyl cellulose, carboxymethyl cellulose, sodium alginate, etc. Among them, when polyvinyl alcohol (PVA) is used as the coating agent for the barrier coating 44, there is a tendency that the gas barrier properties are particularly excellent.
[0185] From the viewpoint of obtaining excellent gas barrier properties, the barrier coating layer 44 may be formed of a composition containing at least one selected from the group consisting of the metal alkoxide represented by the general formula (I) and its hydrolyzate described in the above embodiment.
[0186] Specific examples of metal alkoxides include tetraethoxysilane [Si(OC 2 H 5 ) 4 〕、Triisopropoxyaluminum〔Al(O-2'-C 3 H 7 ) 3 〕 etc. After hydrolysis, tetraethoxysilane and triisopropoxyaluminum tend to be relatively stable in aqueous solvents.
[0187] Examples of the silane coupling agent include the compounds represented by the general formula (II) described in the above embodiment.
[0188] Specific examples of the silane coupling agent include vinyltrimethoxysilane, γ-chloropropylmethyldimethoxysilane, γ-chloropropyltrimethoxysilane, glycidoxypropyltrimethoxysilane, γ-methacryloxypropyltrimethoxysilane, and γ-methacryloxypropylmethyldimethoxysilane.
[0189] In addition, the silane coupling agent can also be a polymer formed by polymerization of the compound represented by the general formula (II). As a polymer, it can be a trimer, or it can be 1,3,5-tris (3-trialkoxysilyl alkyl) isocyanurate. This is a condensation product of 3-isocyanate alkyl alkoxy silane. It is known that in this 1,3,5-tris (3-trialkoxysilyl alkyl) isocyanurate, the isocyanate part has no chemical reactivity, but the reactivity is ensured by the polarity of the urate part. Generally speaking, it is added to adhesives and the like like 3-isocyanate alkyl alkoxy silane, and is known as an adhesion enhancer. Therefore, by adding 1,3,5-tris (3-trialkoxysilyl alkyl) isocyanurate to a hydroxyl-containing polymer compound, the water resistance of the gas barrier coating layer can be improved by utilizing hydrogen bonds. 3-isocyanate alkyl alkoxy silane has high reactivity and low liquid stability. In contrast, 1,3,5-tris(3-trialkoxysilylalkyl)isocyanurate is not water-soluble due to the polarity of the urate portion, but it is easily dispersed in an aqueous solution and can stably maintain liquid viscosity. In addition, 3-isocyanate alkyl alkoxy silane and 1,3,5-tris(3-trialkoxysilylalkyl)isocyanurate have the same water resistance.
[0190] 1,3,5-tris(3-trialkoxysilylalkyl)isocyanurate is also produced by thermal polymerization of 3-isocyanatepropylalkoxysilane, and sometimes contains 3-isocyanatepropylalkoxysilane as a raw material, but there is no particular problem. It may be 1,3,5-tris(3-trialkoxysilylpropyl)isocyanurate or 1,3,5-tris(3-trimethoxysilylpropyl)isocyanurate. 1,3,5-tris(3-trimethoxysilylpropyl)isocyanurate is practically advantageous because the methoxy group hydrolyzes quickly and the one containing the propyl group can be obtained at a relatively low price.
[0191] Furthermore, if necessary, known additives such as an isocyanate compound, a dispersant, a stabilizer, a viscosity modifier, and a colorant may be added to the coating agent within a range that does not impair the gas barrier properties.
[0192] The thickness of the barrier coating 44 may be 50 to 1000 nm, or 100 to 500 nm. When the thickness of the barrier coating 44 is 50 nm or more, more sufficient gas barrier properties tend to be obtained, and when the thickness of the barrier coating 44 is 1000 nm or less, sufficient flexibility tends to be maintained.
[0193] The coating liquid for forming the barrier coating layer 44 can be applied, for example, by dipping, roll coating, gravure coating, reverse gravure coating, air knife coating, comma coating, die coating, screen printing, spray coating, gravure offset printing, etc. The coating film formed by applying the coating liquid can be dried, for example, by hot air drying, hot roll drying, high frequency irradiation, infrared irradiation, UV irradiation, or a combination thereof.
[0194] The temperature during drying of the coating film may be set to, for example, 50 to 150° C. or 70 to 100° C. By setting the drying temperature within the above range, cracks in the vapor deposited layer 43 and the barrier coating layer 44 can be further suppressed, and excellent barrier properties can be exhibited.
[0195] The barrier coating layer 44 can be formed using a coating agent containing a polyvinyl alcohol-based resin and a silane compound. An acid catalyst, a base catalyst, a photopolymerization initiator, etc. can be added to the coating agent as needed.
[0196] The polyvinyl alcohol resin is as described above. In addition, examples of the silane compound include silane coupling agents, polysilazanes, siloxanes, and the like, and specific examples include tetramethoxysilane, tetraethoxysilane, glycidoxypropyltrimethoxysilane, acryloxypropyltrimethoxysilane, and hexamethyldisilazane.
[0197] [Printing layer]
[0198] The laminate 35 may also have a printing layer. The printing layer may be provided on at least one surface of the substrate 41, for example. In order to display relevant information of the contents, identify the contents, improve concealment, or improve the design of the packaging bag, the printing layer is provided at a position visible from the outside of the laminate 35. There are no particular restrictions on the printing method and the printing ink, and they may be appropriately selected from known printing methods and printing inks in consideration of the printing adaptability to the film, the design properties such as the color tone, the tightness, the safety as a food container, and the like. As the printing method, for example, gravure printing, offset printing, gravure offset printing, flexographic printing, inkjet printing, and the like may be used. Among them, from the viewpoint of productivity and high precision of the pattern, the gravure printing method is more likely to be used.
[0199] In order to improve the adhesion of the printed layer, the surface on which the printed layer is provided may be subjected to various pretreatments such as corona treatment, plasma treatment, flame treatment, or provided with a coating such as an easy-adhesion layer.
[0200] [Sealing layer 50]
[0201] The sealing layer 50 is a layer in the laminate 35 that is given sealing properties by heat sealing. From the viewpoint of the recycling suitability of the laminate 35, the sealing layer 50 is a polyolefin film like the substrate 41. In the present embodiment, the sealing layer 50 has a single-layer structure and is a resin layer with polypropylene as the main material, but is not limited to this. The sealing layer 50 may contain a polypropylene film or may be composed of a polypropylene film.
[0202] The polypropylene film may be an acid-modified polypropylene film obtained by graft-modifying polypropylene using unsaturated carboxylic acid, anhydride of unsaturated carboxylic acid, ester of unsaturated carboxylic acid, etc. In addition, examples of polypropylene include polypropylene resins such as homopolymer polypropylene resin (PP), propylene-ethylene random copolymer, propylene-ethylene block copolymer, and propylene-α-olefin copolymer.
[0203] From the viewpoint of improving the sealing property of heat sealing, the polypropylene film constituting the sealant layer 50 may be an unstretched polypropylene film.
[0204] Various additives such as a flame retardant, a slip agent, an anti-blocking agent, an antioxidant, a light stabilizer, a tackifier, and an antistatic agent may be added to the polypropylene film constituting the sealant layer 50 .
[0205] The thickness of the sealant layer 50 is determined by the mass of the content, the shape of the packaging bag, etc., but may be approximately 30 to 150 μm thick, or 50 to 80 μm thick.
[0206] As a method for forming the sealing layer 50, any of the following known methods can be used: a dry lamination method using an adhesive such as a one-component curing type or a two-component curing type polyurethane adhesive to bond the above-mentioned film-like sealing layer composed of the polypropylene; a solvent-free dry lamination method using a solvent-free adhesive to bond the film-like sealing layer; an extrusion lamination method in which the above-mentioned polypropylene is heated and melted, extruded into a curtain shape, and bonded together, etc.
[0207] Among the above forming methods, dry lamination has high resistance to retorting treatment, especially high temperature hot water treatment of 120° C. or higher. On the other hand, the lamination method is not particularly limited if the packaging bag is used for treatment at a temperature of 85° C. or lower.
[0208] [Adhesive layer 60]
[0209] The adhesive layer 60 is a layered component that bonds the barrier layer 40 and the sealing layer 50. As the material of the adhesive contained in the adhesive layer 60, for example, polyester-isocyanate resins, polyurethane resins, polyether resins, etc. can be used. When the packaging bag is used for cooking purposes, a two-component curing urethane adhesive with cooking resistance can be used. In addition, from the perspective of environmental considerations, the adhesive may not contain 3-glycidyloxypropyltrimethoxysilane (GPTMS). The adhesive layer 60 may be chlorine-free. In this case, the coloring of the adhesive forming the adhesive layer 60, the recycled resin after recycling, etc., and the generation of odor caused by heat treatment can be suppressed. From the perspective of environmental considerations, the adhesive layer 60 may be formed of biomass materials or may be solvent-free.
[0210] The thickness of the adhesive layer 60 is 0.5 μm to 10 μm. When the thickness of the adhesive layer 60 is 0.5 μm or more, the peeling of the barrier layer 40 and the sealing layer 50 can be well suppressed. When the thickness of the adhesive layer 60 is 10 μm or less, the laminate 35 can be easily made of a single material (details will be described later). The thickness of the adhesive layer 60 can be 1 μm or more, 2 μm or more, 8 μm or less, 6 μm or less, or 5 μm or less.
[0211] [Polyolefin content]
[0212] The total mass ratio of the polyolefin (in this embodiment, polypropylene) in the laminate 35 is 90 mass % or more. Therefore, the laminate 35 can be said to be a packaging material composed of a single raw material (single material), and has excellent recycling properties. From the viewpoint of further improving recycling properties, the content of the polyolefin in the laminate 35 can be 92.5 mass % or more, or 95 mass % or more, based on the total amount of the laminate 35.
[0213] [Thermal Shrinkage Rate of Base Material 41]
[0214] After the substrate 41 is exposed to 120° C. for 15 minutes (hereinafter referred to as “after heating”), the heat shrinkage rate of the substrate 41 in the MD direction obtained by the above formula (1) described in the first embodiment is 1% or more. For example, after the substrate 41 or the barrier layer 40 containing the substrate 41 is heated in an oven at 120° C. for 15 minutes, the heat shrinkage rate of the substrate 41 in the MD direction obtained by the following formula (1) is 1% or more. From the viewpoint of reducing deformation during bag making and suppressing peeling between the barrier layer 40 and the sealing layer 50, the above heat shrinkage rate in the MD direction is, for example, 12% or less, 11% or less, 10% or less, 9% or less, 8% or less, or 7% or less. In addition, for example, the above heat shrinkage rate of a twin-screw stretched polypropylene film is 1%, while the above heat shrinkage rate of a PET film is less than 1%.
[0215] After the heating, the heat shrinkage rate in the TD direction of the substrate 41 obtained by the above formula (2) described in the first embodiment is not particularly limited, and is, for example, 1% or more. From the viewpoint of reducing deformation during bag making and suppressing peeling between the barrier layer 40 and the sealant layer 50, the heat shrinkage rate in the TD direction is, for example, 12% or less, 11% or less, 10% or less, 9% or less, 8% or less, or 7% or less.
[0216] [Hardness of Adhesive Layer 60]
[0217] Based on the above-mentioned heat shrinkage rate of the substrate 41, in the present embodiment, after the stack 35 is subjected to the retort treatment, the hardness of the adhesive layer 60 is 0.1 MPa or more and less than 0.9 MPa. In this case, the adhesive layer 60 can well follow the expansion and contraction of the substrate 41 accompanied by the heat treatment such as the retort treatment and the boiling treatment. Therefore, even if the above-mentioned heat treatment is applied to the stack 35 including the substrate 41 having the above-mentioned heat shrinkage rate, it is not easy to peel off between the barrier layer 40 and the sealing layer 50. In addition, the generation of cracks in the adhesive layer 60 during the cooling after the above-mentioned heat treatment, and the generation of damage to the barrier layer 40 (at least one of the adhesion layer 42, the vapor-deposited layer 43 and the barrier coating layer 44) accompanying the generation of the cracks are suppressed. The hardness of the adhesive layer 60 before the retort treatment is not particularly limited, but is, for example, 1.0 MPa or more.
[0218] The hardness of the adhesive layer 60 can be controlled by the material of the adhesive, the amount of curing agent, the aging time, etc. The narrower the distance between the molecular chains of the adhesive, the harder the adhesive layer 60 tends to be. The more voluminous the adhesive is, the softer the adhesive layer 60 tends to be. The hardness of the aliphatic adhesive layer 60 tends to be harder than that of the alicyclic or aromatic adhesive layer 60. The hardness of the alicyclic adhesive layer 60 tends to be harder than that of the aromatic adhesive layer 60. The more the amount of curing agent contained in the adhesive layer 60, the harder the adhesive layer 60 tends to be. The longer the aging time, the harder the adhesive layer 60 tends to be.
[0219] The hardness of the adhesive layer 60 in the stack 35 can be obtained by measuring the hardness of the portion (exposed portion) exposed from the sealing layer 50. The removal of the sealing layer 50 to expose the adhesive layer 60 can be implemented, for example, using an oblique cutting device. In the present embodiment, the hardness of the adhesive layer 60 can be measured and obtained by the nanoindentation method. The nanoindentation method refers to a measurement method in which a quasi-static extrusion test using an indenter is performed on a target measurement object (specimen) to obtain the mechanical properties of the sample. The hardness of a sample such as the adhesive layer 60 is calculated, for example, by the following method. First, fused quartz is preliminarily tested as a standard sample, and the relationship between the contact depth and the contact projection area between the indenter and the sample is calibrated. Thereafter, the hardness of the sample is calculated by analyzing the unloading curve in the region of 20% to 95% relative to the maximum load during unloading using the Oliver-Pharr method.
[0220] <Packaging bag>
[0221] Below, refer to Figure 6 An example of a packaging bag as a bag-made product of the laminate 35 will be described. Figure 6 This is a schematic top view of an example of a packaging bag. Figure 6 The packaging bag 100 shown is formed into a bag shape by, for example, sealing the ends of a stacked body 35 folded in half with the contents interposed therebetween.
[0222] The packaging bag 100 is a three-side sealed bag, which has a main body 101 for storing contents, a sealing portion 102 located at the end of the main body 101, and a bent portion 103 where the laminate 35 is bent. The shape of the main body 101 is not particularly limited, for example, it is rectangular when viewed from a specified direction. Printing can be implemented on at least a portion of the outer surface of the main body 101. In the main body 101, in addition to the contents, for example, a specific gas such as nitrogen can also be stored. The sealing portion 102 is a portion where a portion of the sealing layer 50 of the laminate 35 is bonded to other portions. In the sealing portion 102, a portion of the sealing layer 50 of the laminate 35 is in close contact with other portions. The sealing portion 102 is formed, for example, by heating and compressing a portion of the sealing layer 50 of the laminate 35 and other portions (i.e., heat sealing), but is not limited thereto. For example, the sealing portion 102 can also be formed by cold sealing, etc. In the packaging bag 100 , the folded portion 103 constitutes one side of the main body 101 , and the seal portion 102 constitutes the remaining three sides of the main body 101 . Both ends of the folded portion 103 overlap with the seal portion 102 .
[0223] After the laminate 35 of the present embodiment described above is subjected to retort treatment, the hardness of the adhesive layer 60 measured by the nanoindentation method is 0.1 MPa or more and less than 0.9 MPa. Thus, by using the substrate 41 having a heat shrinkage rate of 1% or more in the MD direction, even if the substrate 41 expands and contracts with the retort treatment, the adhesive layer 60 can follow it well. Therefore, damage to the barrier coating 44 caused by the generation of cracks in the adhesive layer 60 can be suppressed. Therefore, it is possible to provide a laminate 35 that can well exhibit gas barrier properties (especially oxygen permeation prevention performance) even after the retort treatment.
[0224] In one example, the barrier layer 40 includes an adhesion layer 42 and a vapor-deposited layer 43 located between the substrate 41 and the barrier coating layer 44, and the adhesion layer 42 is located between the substrate 41 and the vapor-deposited layer 43. Therefore, compared with the case where the barrier layer includes only the substrate 41 and the barrier coating layer 44, the gas barrier property of the laminate 35 can be improved.
[0225] In one example, the thickness of the vapor deposition layer 43 may be 5 nm to 80 nm. In this case, the vapor deposition layer 43 can be prevented from being cracked and the gas barrier property can be improved.
[0226] In one example, the thickness of the adhesive layer 60 may be 0.5 μm to 10 μm. In this case, the laminate 35 can be easily made of a single material while the separation between the barrier layer 40 and the sealant layer 50 is well suppressed.
[0227] In one example, the substrate 41 and the sealant layer 50 are each a polyolefin film, and the total mass ratio of the polyolefin in the laminate 35 may be 90 mass % or more. In this case, a single material can be achieved.
[0228] In one example, the base material 41 may be a stretched polypropylene film, and the sealant layer 50 may be an unstretched polypropylene film. In this case, the laminate 35 has excellent heat resistance to retort treatment or the like.
[0229] Next, refer to Figure 7 A modification of the second embodiment will be described. The descriptions that overlap with the above embodiment will be omitted, and only the parts that are different from the above embodiment will be described. That is, the description of the above embodiment can also be appropriately used in the modification within the technically feasible range.
[0230] Figure 7 Schematic cross-sectional view of a laminated body showing a modified example. Figure 7As shown, the laminate (packaging film) 35A has, in addition to the barrier layer 40, the sealant layer 50 and the adhesive layer 60, an outermost layer 70 overlapping the barrier layer 40, and a second adhesive layer 60A that adheres the outermost layer 70 and the barrier layer 40. In this modification, the sealant layer 50, the adhesive layer 60, the barrier layer 40, the second adhesive layer 60A and the outermost layer 70 are stacked in sequence. In addition, the adhesive layer 60, the substrate 41, the close-fitting layer 42, the vapor-deposited layer 43, the barrier coating layer 44, the second adhesive layer 60A and the outermost layer 70 are stacked in sequence. Therefore, the adhesive layer 60 adheres to the substrate 41 and the sealant layer 50, and the second adhesive layer 60A adheres to the barrier coating layer 44 and the outermost layer 70. In this modification, the barrier layer 40 functions as an intermediate layer in the laminate 35A.
[0231] [Outermost layer 70]
[0232] The outermost layer 70 is a plastic member that functions as the outermost member in the stack 35A. The outermost layer 70 has the same functions and performance as the base material 41. For example, the thickness of the outermost layer 70 is about the same as the thickness of the base material 41. From the viewpoint of the recycling adaptability of the stack 35A, the outermost layer 70 is, for example, a polyolefin film. From the viewpoint of heat resistance, the outermost layer 70 may contain a polypropylene film or may be composed of a polypropylene film.
[0233] In this modification, after the outermost layer 70 is exposed to 120° C. for 15 minutes, the heat shrinkage rate of the outermost layer 70 in the MD direction obtained by the above formula (1) is 1% or more. For example, after the outermost layer 70 or the laminate of the outermost layer 70 and the barrier layer 40 is heated in an oven at 120° C. for 15 minutes, the heat shrinkage rate of the outermost layer 70 in the MD direction obtained by the above formula (1) is 1% or more. The above heat shrinkage rate in the MD direction is, for example, 12% or less, 11% or less, 10% or less, 9% or less, 8% or less, or 7% or less.
[0234] The heat shrinkage rate in the TD direction of the outermost layer 70 obtained by the above formula (2) after the above heating is not particularly limited, and is, for example, 1% to 12%.
[0235] [Second Adhesive Layer 60A]
[0236] The second adhesive layer 60A is a layered component that bonds the barrier layer 40 and the outermost layer 70. The material of the adhesive contained in the second adhesive layer 60A is the same as the material of the adhesive contained in the adhesive layer 60. The thickness of the second adhesive layer 60A is the same as the thickness of the adhesive layer 60, which is 0.5μm to 10μm. In this modification, after the stack 35A is subjected to a steaming treatment, the hardness of the second adhesive layer 60A is greater than 0.1MPa and less than 0.9MPa. In this case, the second adhesive layer 60A can well follow the expansion and contraction of the outermost layer 70 accompanied by a heating treatment such as a steaming treatment and a boiling treatment. Therefore, even if the above-mentioned heating treatment is applied to the stack 35A including the second adhesive layer 60A having the above-mentioned heat shrinkage rate, peeling between the barrier layer 40 and the outermost layer 70 is not easy to occur. In addition, the generation of cracks in the second adhesive layer 60A during cooling after the above-mentioned heat treatment and the generation of damage to the barrier layer 40 (at least one of the adhesion layer 42, the vapor-deposited layer 43, and the barrier coating layer 44) accompanying the generation of the cracks are suppressed. The hardness of the second adhesive layer 60A before the steaming treatment is not particularly limited, but is, for example, 1.0 MPa or more.
[0237] The hardness of the second adhesive layer 60A can be controlled by the material of the adhesive, the amount of the curing agent, the aging time, etc. The narrower the distance between the molecular chains of the adhesive, the more the second adhesive layer 60A tends to become hard. The more voluminous the adhesive, the softer the second adhesive layer 60A tends to become. The hardness of the aliphatic second adhesive layer 60A tends to become hard compared with the alicyclic or aromatic second adhesive layer 60A. The hardness of the alicyclic second adhesive layer 60A tends to become hard compared with the aromatic second adhesive layer 60A.
[0238] The greater the amount of curing agent contained in the second adhesive layer 60A, the harder the second adhesive layer 60A tends to become. The longer the aging time, the harder the second adhesive layer 60A tends to become.
[0239] The above-described modified example also exhibits the same effects as those of the second embodiment. In addition, the barrier layer 40 can be protected by the outermost layer 70 .
[0240] The gas barrier film, packaging film, and packaging bag according to one aspect of the present disclosure are described in, for example, [1] to
[19] below, and are described in detail based on the above-mentioned embodiment and the above-mentioned modification examples.
[0241] [1] A gas barrier film comprising, in this order, a base layer containing a polypropylene resin, a vapor-deposited layer containing an inorganic oxide, and a gas barrier coating layer,
[0242] The base material layer includes a first surface layer and a core layer, and the vapor-deposited layer is formed on the first surface layer side.
[0243] The hardness of the first surface layer measured by nanoindentation method is 0.02-0.15 GPa, the hardness of the core layer is above 0.07 GPa, and the hardness of the core layer is greater than that of the first surface layer.
[0244] [2] The gas barrier film according to [1], wherein the first surface layer contains a propylene-α-olefin copolymer.
[0245] [3] The gas barrier film according to [1] or [2], wherein a ratio of the thickness of the first skin layer to the thickness of the core layer is 1 / 100 to 1 / 5.
[0246] [4] The gas barrier film according to any one of [1] to [3], wherein the complex elastic modulus of the first surface layer measured by nanoindentation is 1.2 to 2.5 GPa, and the complex elastic modulus of the core layer is 2.0 GPa or more.
[0247] [5] The gas barrier film according to any one of [1] to [4], wherein the inorganic oxide contains at least one of aluminum oxide and silicon oxide.
[0248] [6] The gas barrier film according to any one of [1] to [5], wherein the gas barrier coating layer is formed from a cured product of a composition containing: a water-soluble polymer having a hydroxyl group and at least one selected from a metal alkoxide, a silane coupling agent, and hydrolyzates thereof.
[0249] [7] The gas barrier film according to any one of [1] to [6], further comprising an anchor coating layer between the substrate layer and the vapor-deposited layer.
[0250] [8] The gas barrier film according to any one of [1] to [7], wherein the base layer has the first surface layer, the core layer, and the second surface layer in this order.
[0251] [9] The gas barrier film according to [8], wherein the second surface layer contains a propylene-α-olefin copolymer.
[0252]
[10] The gas barrier film according to [8] or [9], wherein the hardness of the second surface layer measured by a nanoindentation method is 0.02 to 0.15 GPa.
[0253]
[11] The gas barrier film according to any one of [1] to
[10] , wherein the vapor deposited layer has a thickness of 5 nm to 80 nm.
[0254]
[12] A packaging film comprising:
[0255] The gas barrier film according to any one of [1] to
[11] ,
[0256] a sealing layer overlapping the gas barrier coating layer, and
[0257] The gas barrier coating layer and the sealing layer are bonded together with an adhesive layer containing a two-component curing urethane adhesive,
[0258] After the packaging film is subjected to a retort treatment, the hardness of the adhesive layer measured by a nanoindentation method is 0.1 MPa or more and less than 0.9 MPa.
[0259]
[13] The packaging film according to
[12] , wherein the hardness of the adhesive layer measured by a nanoindentation method before the retort treatment is 1.0 MPa or more.
[0260]
[14] The packaging film according to
[12] or
[13] , wherein the adhesive layer has a thickness of 0.5 μm to 10 μm.
[0261]
[15] The packaging film according to any one of
[12] to
[14] , wherein the substrate layer and the sealant layer are each a polyolefin film,
[0262] The proportion of the total mass of the polyolefin in the packaging film is 90 mass % or more.
[0263]
[16] The packaging film according to any one of
[12] to
[15] , wherein the base layer is a stretched polypropylene film, and the sealant layer is an unstretched polypropylene film.
[0264]
[17] The packaging film according to any one of
[12] to
[16] , further comprising an outermost layer overlapping the substrate layer, and a second adhesive layer bonding the outermost layer and the substrate layer.
[0265] The adhesive layer bonds the base material layer and the sealing layer.
[0266] The second adhesive layer bonds the substrate and the outermost layer.
[0267]
[18] The packaging film according to
[17] , wherein after the outermost layer is exposed to 120° C. for 15 minutes, the heat shrinkage rate of the outermost layer in the MD direction calculated by the following formula (1) is 1% or more,
[0268] After the packaging film is subjected to a retort treatment, the hardness of the second adhesive layer measured by a nanoindentation method is 0.1 MPa or more and less than 0.9 MPa.
[0269] Heat shrinkage ratio in MD direction (%)=(length in MD direction before heating−length in MD direction after heating) / length in MD direction before heating×100(1).
[0270]
[19] A packaging bag, which is a bag made of the packaging film according to any one of
[12] to
[18] .
[0271] However, one aspect of the present disclosure is not limited to the above-mentioned embodiment, the above-mentioned modification example, and the above-mentioned [1] to
[19] . One aspect of the present disclosure can be further modified within the scope not departing from the gist thereof.
[0272] In the second embodiment and its variant, the total mass ratio of the polypropylene in the laminate can be 90% by mass or more. Therefore, for example, in the laminate of the variant, the mass ratio of the polypropylene in one of the substrate and the outermost layer can be less than 90% by mass. Alternatively, in the laminate, the mass ratio of the polypropylene in the barrier layer can be less than 90% by mass.
[0273] In the above-mentioned second embodiment and its variant, an adhesion-enhancing coating and a vapor-deposited layer are provided on the substrate, but it is not limited thereto. For example, a vapor-deposited layer may be provided on the sealing layer. In this case, an adhesion-enhancing coating may be provided between the sealing layer and the vapor-deposited layer. In this case, the sealing layer and the adhesion-enhancing coating may be co-extruded layers. Alternatively, an adhesion-enhancing coating and a vapor-deposited layer may be provided on the substrate, and a vapor-deposited layer may be provided on the sealing layer. Alternatively, an adhesion-enhancing coating may not be provided.
[0274] Example
[0275] Hereinafter, the present invention will be described in more detail by way of examples, but the present invention is not limited to these examples. First, Examples 1 to 38, Comparative Examples 1 to 3, and Reference Examples 1 to 3 will be described.
[0276] <Production of Gas Barrier Film>
[0277] (Example 1)
[0278] Ethylene-1-butene-propylene random copolymer resin (ethylene content: 2.5 mol%, 1-butene content: 3.5 mol%) was prepared as the material of the surface layer, and homopolymer polypropylene resin was prepared as the material of the core layer. After these resins were co-extruded, a substrate film (substrate layer) with a total thickness of 20 μm was prepared by twin-screw stretching. The thickness of the surface layer was 0.7 μm, and the thickness of the core layer was 19.3 μm.
[0279] On the surface of the substrate layer, an acrylic primer solution was applied by gravure coating and dried to form an anchor coating layer with a thickness of 0.1 μm. Next, a silicon oxide thin film with a thickness of 30 nm was deposited on the anchor coating layer by reactive vapor deposition using high-frequency excitation ion plating in an oxygen atmosphere under reduced pressure to form an inorganic oxide vapor-deposited layer.
[0280] Tetraethoxysilane (hereinafter referred to as "TEOS"), methanol and 0.1N hydrochloric acid were mixed in a mass ratio of 45 / 15 / 40 to obtain a TEOS hydrolyzed solution. This solution, a 5 mass % aqueous solution of polyvinyl alcohol (hereinafter referred to as "PVA"), and a solution of 1,3,5-tris(3-methoxysilylpropyl)isocyanurate in a mass ratio of water / IPA (isopropyl alcohol) of 1 / 1 were mixed so that the solid content reached 5 mass % (converted to R 2 Si(OH) 3 ) were mixed to prepare a coating solution (composition for forming a gas barrier coating layer). The coating solution was prepared according to the SiO 2 Solid content (converted value) and R of isocyanurate silane 2 Si(OH) 3 The solution was prepared so that the mass ratio of the solid content (converted value) to the PVA solid content was 40 / 5 / 55. The coating solution was applied on the vapor deposited layer by gravure coating and then dried at 80°C for 60 seconds to form a gas barrier coating layer with a thickness of 0.3 μm.
[0281] In this way, a gas barrier film of Example 1 having a laminated structure of gas barrier coating layer / vapor deposited layer / anchor coating layer / surface layer / core layer was obtained.
[0282] (Example 2)
[0283] A gas barrier film was obtained by the same operation as in Example 1 except that an ethylene-propylene random copolymer resin (ethylene content: 5.0 mol %) was used as the material of the surface layer.
[0284] (Example 3)
[0285] A gas barrier film was obtained by the same operation as in Example 1 except that an ethylene-propylene random copolymer resin (ethylene content: 3.2 mol %) was used as the material of the surface layer.
[0286] (Example 4)
[0287] A gas barrier film was obtained by the same operation as in Example 1 except that an ethylene-propylene random copolymer resin (ethylene content: 7.5 mol %) was used as the material of the surface layer.
[0288] (Comparative Example 1)
[0289] A gas barrier film was obtained by the same operation as in Example 1 except that a base film having only a core layer and no skin layer was formed was used.
[0290] (Comparative Example 2)
[0291] A gas barrier film was obtained by the same operation as in Example 1 except that an ethylene-1-butene-propylene random copolymer resin (ethylene content: 5 mol %, 1-butene content: 6 mol %) was used as the material of the surface layer.
[0292] (Comparative Example 3)
[0293] A gas barrier film was obtained by the same operation as in Example 1 except that an ethylene-propylene random copolymer resin (ethylene content: 0.5 mol %) was used as the material of the surface layer.
[0294] <Production of packaging film>
[0295] On the gas barrier coating layer side of the gas barrier film produced in each example, an unstretched polypropylene film having a thickness of 60 μm was laminated by dry lamination via a two-component curable urethane adhesive to obtain a packaging film.
[0296] (Example 5)
[0297] Ethylene-1-butene-propylene random copolymer resin (ethylene content: 2.5 mol%, 1-butene content: 3.5 mol%) was prepared as the material of the first surface layer, homopolypropylene resin was prepared as the material of the core layer, and ethylene-propylene random copolymer resin (ethylene content: 7.5 mol%) was prepared as the material of the second surface layer. After the above resins were co-extruded, a substrate film (substrate layer) with a total thickness of 20 μm was prepared by twin-screw stretching. The thickness of the first surface layer and the second surface layer was 0.7 μm, and the thickness of the core layer was 18.6 μm.
[0298] Next, the same operation as in Example 1 was performed on the first surface layer of the substrate layer to stack the layers, thereby obtaining a gas barrier film of Example 5 having a stacked structure of gas barrier coating layer / evaporated layer / anchor coating layer / first surface layer / core layer / second surface layer.
[0299] (Example 6)
[0300] A gas barrier film was obtained by the same operation as in Example 5 except that an ethylene-propylene random copolymer resin (ethylene content: 5.6 mol %) was used as the material of the second surface layer.
[0301] (Example 7)
[0302] A gas barrier film was obtained by the same operation as in Example 1 except that the surface of the core layer opposite to the surface on which the first skin layer was laminated was subjected to corona treatment.
[0303] (Reference Example 1)
[0304] A gas barrier film was obtained by the same operation as in Example 6 except that a homopolypropylene resin was used as the material of the second surface layer.
[0305] (Reference Example 2)
[0306] A gas barrier film was obtained by the same operation as in Example 6 except that an ethylene-propylene random copolymer resin (ethylene content: 0.7 mol %) was used as the material of the second surface layer.
[0307] (Reference Example 3)
[0308] A gas barrier film was obtained by the same operation as in Example 6 except that an ethylene-1-butene-propylene random copolymer resin (ethylene content: 5 mol %, 1-butene content: 6 mol %) was used as the material of the second surface layer.
[0309] <Production of packaging film>
[0310] On the gas barrier coating layer side of the gas barrier film produced in each example, a 20 μm thick stretched polypropylene film was laminated by dry lamination via a two-component curable urethane adhesive. In addition, on the substrate layer side of the gas barrier film, a 60 μm thick unstretched polypropylene film was laminated by dry lamination via a two-component curable urethane adhesive. Thus, a packaging film was obtained.
[0311] (Example 8)
[0312] A gas barrier film was obtained by the same operation as in Example 1 except that a water-based polyurethane resin (Takeluck WPB-341 manufactured by Mitsui Chemicals, Inc.) was applied on the surface of the substrate layer by gravure coating and dried to form an anchor coating layer having a thickness of 1.5 μm.
[0313] (Example 9)
[0314] A gas barrier film was obtained by the same operation as in Example 1 except that the thickness of the skin layer was 0.3 μm and the thickness of the core layer was 19.7 μm.
[0315] (Example 10)
[0316] A gas barrier film was obtained by the same operation as in Example 1 except that the thickness of the surface layer was 1.5 μm, the thickness of the core layer was 16.5 μm, and the thickness of the adhesive coating layer was 1.1 μm.
[0317] (Example 11)
[0318] A gas barrier film was obtained by the same operation as in Example 1 except that the material of the surface layer was set to a butene-propylene random copolymer resin (butene content: 2.5 mol %), the thickness of the surface layer was set to 0.7 μm, and the thickness of the anchor coating layer was set to 2.1 μm.
[0319] (Example 12)
[0320] A gas barrier film was obtained by the same operation as in Example 1 except that the material of the surface layer was set to a butene-propylene random copolymer resin (butene content: 1.0 mol %), the thickness of the surface layer was set to 0.7 μm, and the thickness of the anchor coating layer was set to 3.1 μm.
[0321] (Example 13)
[0322] The thickness of the anchor coating layer was set to 4.1 μm, and the coating liquid (gas barrier coating layer-forming composition) was adjusted so that the SiO 2 Solid content (converted value) and R of isocyanurate silane 2 Si(OH) 3 A gas barrier film was obtained by the same operation as in Example 1 except that the solution was adjusted so that the mass ratio of the solid content (converted value) to the PVA solid content was 45 / 10 / 45.
[0323] (Example 14)
[0324] The thickness of the anchor coating layer was set to 5.1 μm, and the coating liquid (gas barrier coating layer-forming composition) was adjusted so that the SiO 2 Solid content (converted value) and R of isocyanurate silane 2 Si(OH) 3 A gas barrier film was obtained by the same operation as in Example 1 except that the solution was adjusted so that the mass ratio of the solid content (converted value) to the PVA solid content was 45 / 7 / 48.
[0325] <Production of packaging film>
[0326] On the gas barrier coating layer side of the gas barrier film produced in each example, an unstretched polypropylene film having a thickness of 60 μm was laminated by dry lamination via a two-component curable urethane adhesive to obtain a packaging film.
[0327] <Evaluation>
[0328] (Preparation of Samples for Nanoindentation Measurement)
[0329] The front and back surfaces of the gas barrier film produced in each example were corona treated at 0.20 kW (apparatus: corona treater CT-0212 manufactured by Kasuga Electric Co., Ltd.), and then the film was cut into a wedge shape with a base of 1.0 mm×height of 5.0 mm using a razor.
[0330] The cut film was embedded in a photocurable resin and cured using a halogen lamp KTX-100R (manufactured by Kencon Tokina Co., Ltd.) D-800 manufactured by Toagosei Co., Ltd. was used as the photocurable resin.
[0331] The film embedding resin after photocuring was fixed with an insert using an AFM sample holder, and the cross section of the film was cut with a glass knife at room temperature (25°C). Then, the final cross section cutting was performed at room temperature with a diamond tool with a cutting speed of 1.0 mm / s and a cutting layer thickness of 100 nm, and the cutting was terminated when the mirror surface was formed. As the cross section cutting device, an ultramicrotome (EMUC7 manufactured by Lai Ka Co., Ltd.) and a cryogenic system (EM FC7 manufactured by Lai Ka Co., Ltd.) were used. In addition, the cutting direction of the knife was parallel to the layer interface.
[0332] (Nanoindentation measurement)
[0333] Hysitron TI-Premier (trade name) manufactured by Fukurum Co., Ltd. was used as the measuring device, and a Berkovich-type diamond indenter manufactured by Fukuoka Co., Ltd. was used as the indenter.
[0334] The measurement by the nanoindentation method was performed in a displacement control mode, with the indentation speed of 30 nm / sec to a depth of 30 nm, the maximum depth was maintained for 1 second, and then unloaded at a speed of 30 nm / sec.
[0335] The measurement was performed by obtaining a shape image of the sample cross section using a shape measurement function of a measuring device that scans the sample surface with an indenter, and specifying 20 points at intervals of 1 μm or more on the target layer based on the shape image.
[0336] When calculating the hardness and complex elastic modulus, fused silica is tested as a standard sample in advance to calibrate the relationship between the contact depth and contact projection area between the indenter and the sample. Then, the unloading curve in the region of 60% to 95% of the maximum load during unloading is analyzed using the Oliver-Pharr method to calculate the hardness and complex elastic modulus.
[0337] (Steaming treatment)
[0338] Using the packaging film produced in each example, a packaging bag with four sides as sealed portions was produced. The packaging bag was filled with water as the content and then subjected to retort sterilization treatment at 130° C. for 30 minutes.
[0339] (Oxygen permeability measurement)
[0340] The oxygen permeability of the packaging film after retorting was measured. The measurement was carried out using an oxygen permeability measuring device (modern control company, OXTRAN 2 / 20) at a temperature of 30°C and a relative humidity of 70%. The measurement method was based on JIS K-7126, B method (isobaric method) and ASTM D3985-81, and the measured value was expressed in [cm 3 (STP) / m2 ·day·atm] indicates.
[0341] (Lamination strength measurement)
[0342] The lamination strength between the gas barrier film and the unstretched polypropylene film was measured for the packaging film after the retort treatment. The measurement was carried out in accordance with JIS K6854 at a test width of 15 mm, a peeling speed of 300 mm / min, and a peeling angle of 180 degrees. The measured value is expressed in the unit [N / 15mm]. In addition, in Examples 1 to 4 and Comparative Examples 1 to 3, the lamination strength between the first surface layer and the unstretched polypropylene film was measured. In Examples 5 to 7 and Reference Examples 1 to 3, the lamination strength between the second surface layer and the unstretched polypropylene film was measured.
[0343] The conditions of each example and the evaluation results of each example are shown in Tables 1 to 6. In each table, ethylene-1-butene-propylene random copolymer resin is recorded as "EBP", ethylene-propylene random copolymer resin is recorded as "EP", butene-propylene random copolymer resin is recorded as "BP", homopolymer polypropylene resin is recorded as "HPP", acrylic primer solution is recorded as "acrylic acid", water-based polyurethane resin is recorded as "urethane", silicon oxide is recorded as "SiOx", aluminum oxide is recorded as "AlOx", and isocyanurate silane is recorded as "SC". In the case where the core layer is subjected to corona treatment, it is recorded as "HPP (corona treatment)".
[0344] From the results shown in Tables 1 to 6, it was clearly confirmed that the packaging films using the gas barrier films of Examples could suppress the oxygen permeability to a low level even after heat sterilization and that the lamination strength between the layers was excellent.
[0345] From the results shown in Tables 3 and 4, it was clearly confirmed that providing a second skin layer on the core layer or performing a corona treatment has the effect of improving the lamination strength of the layer adjacent to the base material layer.
[0346] Table 1
[0347] Table 2
[0348]
[0349] Table 3
[0350]
[0351] Table 4
[0352]
[0353] Table 5
[0354]
[0355] Table 6
[0356]
[0357] (Example 15)
[0358] On the gas barrier coating layer side of the gas barrier film produced in Example 1, a 60 μm thick unstretched polypropylene film was laminated by dry lamination via a two-component curable urethane adhesive (a) to obtain a packaging film.
[0359] (Examples 16 to 20)
[0360] Packaging films of Examples 16 to 20 were obtained in the same manner as in Example 15 except that two-component curable urethane adhesives (b) to (f) were used instead of the adhesive (a).
[0361] (Example 21)
[0362] On the gas barrier coating layer side of the gas barrier film produced in Example 2, a 60 μm thick unstretched polypropylene film was laminated by dry lamination via a two-component curable urethane adhesive (a) to obtain a packaging film.
[0363] (Examples 22 to 26)
[0364] Packaging films of Examples 24 to 28 were obtained in the same manner as in Example 21 except that two-component curable urethane adhesives (b) to (f) were used instead of the adhesive (a).
[0365] (Example 27)
[0366] On the gas barrier coating layer side of the gas barrier film produced in Example 3, a 60 μm thick unstretched polypropylene film was laminated by dry lamination via a two-component curable urethane adhesive (a) to obtain a packaging film.
[0367] (Examples 28 to 32)
[0368] Packaging films of Examples 28 to 32 were obtained in the same manner as in Example 27 except that two-component curable urethane adhesives (b) to (f) were used instead of the adhesive (a).
[0369] (Example 33)
[0370] On the gas barrier coating layer side of the gas barrier film produced in Example 4, a 60 μm thick unstretched polypropylene film was laminated by dry lamination via a two-component curable urethane adhesive (a) to obtain a packaging film.
[0371] (Examples 34 to 38)
[0372] Packaging films of Examples 34 to 48 were obtained in the same manner as in Example 33 except that two-component curable urethane adhesives (b) to (f) were used instead of the adhesive (a).
[0373] <Evaluation>
[0374] (Steaming treatment)
[0375] Using the packaging film produced in each example, a packaging bag with four sides as sealed portions was produced. The packaging bag was filled with water as the content and then subjected to retort sterilization treatment at 130° C. for 60 minutes.
[0376] (Measurement of hardness of adhesive layer)
[0377] In Examples 15 to 38, a packaging film as a part of a packaging bag after retorting was cut out. Then, an epoxy adhesive (manufactured by Conisy Co., Ltd., trade name: Bond E-Set) was applied to the base layer of the cut packaging film. Then, the packaging film was attached to a glass plate via the epoxy adhesive, thereby forming a sample having a packaging film smoothly fixed to the glass plate.
[0378] After the epoxy adhesive is cured, a sample is set on an oblique cutting device (manufactured by Dypro Instruments Co., Ltd., trade name: SAICASDN-GS). Next, after a diamond cutting blade with a V-shaped front end is installed on the oblique cutting device, a side cut line is formed on the surface of the sealing layer at a width interval of 1 mm. Next, a diamond knife with a blade width of 1 mm, a front angle of 20 degrees, and a back angle of 10 degrees is brought into contact with the surface of the sealing layer with a load of 0.05 N, and the sealing layer is obliquely cut under the conditions of a horizontal speed of 50 μm / s and a vertical speed of 1 μm / s. At this time, first, after the cutting depth reaches 55 μm, 10 mm is cut horizontally. Then, fine cutting is performed with a cutting depth of 1 μm under the conditions of a horizontal speed of 50 μm / s and a vertical speed of 1 μm / s. Observe the exposed surface after cutting, and add the number of fine cutting times as needed until the exposed surface of the desired adhesive layer is obtained. As described above, the preparation for measuring the hardness of the adhesive layer after the retort treatment by the nanoindentation method (ie, the preparation for exposing the adhesive layer) is completed.
[0379] Next, as a device for measuring the hardness of the adhesive layer by nanoindentation, Hysitron TI-Premier (trade name) manufactured by Bruka Japan Co., Ltd. was used. In addition, as an indenter, a Berkovich-type diamond indenter manufactured by Bruka Japan Co., Ltd. was used. Then, after the sample with the adhesive layer exposed was set on the above-mentioned device, the indentation speed was set to 100nm / second and the test depth was set to 125nm in the displacement control mode, and the indenter was pressed into the sample at room temperature (25°C). Then, after the maximum displacement was maintained for 2 seconds, it was unloaded at a speed of 50nm / second. The surface load was set to 1μN, and the surface correction was performed using the TriboScan software. The measurement position is to observe the optical microscope image, and the sample surface, that is, the exposed surface of the adhesive layer (the position of 1 / 4 of the distance from the sealant side when the distance between the sealing layer and the substrate layer is divided into 4 equal parts on the exposed surface) is designated at 30 points at intervals of more than 30 μm, and the measurement is performed using the nanoindentation method. The hardness of the adhesive layer is calculated by first pre-testing fused quartz as a standard sample and calibrating the relationship between the contact depth and contact projection area between the indenter and the sample. Then, the unloading curve in the area of 20 to 95% of the maximum load during unloading is analyzed using the Oliver-Pharr method to calculate the hardness.
[0380] (Oxygen permeability)
[0381] The oxygen permeability of the packaging film after the retort treatment was measured in the same manner as above.
[0382] (Lamination strength measurement)
[0383] The lamination strength between the gas barrier film after the retort treatment and the unstretched polypropylene film was measured in the same manner as described above.
[0384] The conditions and evaluation results of each example are shown in Table 7. As is clear from the results shown in Table 7, the greater the hardness of the adhesive layer, the higher the oxygen permeability measurement result. In addition, it was confirmed that the lamination strength was excellent similarly to Examples 1 to 14.
[0385] Table 7
[0386]
[0387] Next, Examples 45 to 80 and Comparative Examples 5 to 24 are described.
[0388] <Base material, outermost layer and sealing layer>
[0389] As the substrate and the outermost layer, a twin-screw stretched polypropylene (OPP) film (Mitsui Chemicals Toselo Co., Ltd., trade name: ME-1, thickness: 20 μm) was prepared. In addition, as the sealant layer, an unstretched polypropylene (CPP) film (Toray Film Processing Co., Ltd., trade name: Toray Fan ZK 93KM, thickness: 60 μm) was prepared.
[0390] <Preparation of Adhesion Layer Forming Composition>
[0391] A mixed solution was generated by mixing and stirring γ-isocyanate propyl trimethoxysilane: acrylic polyol in a ratio of 1:5. Next, toluene diisocyanate (TDI) was added to the mixed solution so that the number of NCO groups of toluene diisocyanate and the number of OH groups of acrylic polyol were equal. Then, the mixed solution was diluted with ethyl acetate to 2% by mass. Thus, a composition for forming a close-fitting layer (adhesive coating agent) was prepared.
[0392] <Preparation of Barrier Coating Liquid α>
[0393] 10 g of each of the following liquid A, liquid B, and liquid C were prepared and mixed to prepare a coating liquid α.
[0394] Liquid A: In tetraethoxysilane (Si(OC 2 H 5 ) 4 ) 17.9g and methanol 10g were added with 72.1g of 0.1N hydrochloric acid, and the mixture was stirred for 30 minutes and hydrolyzed to obtain a solid content of 5% by mass (converted to SiO 2 )'s hydrolysis solution.
[0395] Solution B: 5 mass % water / methanol solution of polyvinyl alcohol (mass ratio of water:methanol is 95:5).
[0396] Solution C: 1,3,5-tris(3-trialkoxysilylpropyl)isocyanurate was diluted with a mixed solution of water / isopropyl alcohol (mass ratio of water:isopropyl alcohol: 1:1) to a hydrolysis solution having a solid content of 5% by mass.
[0397] <Preparation of Barrier Coating Liquid β>
[0398] First, TEOS, methanol and 0.1N hydrochloric acid were mixed in a mass ratio of 45 / 15 / 40 to obtain a TEOS hydrolyzed solution. This solution, a 5 mass % aqueous solution of polyvinyl alcohol (hereinafter referred to as "PVA"), and a silane coupling agent 1,3,5-tris(3-methoxysilylpropyl)isocyanurate solution of water / IPA (isopropyl alcohol) = 1 / 1 were diluted to a solid content of 5 mass % (converted to R 2 Si(OH) 3) and the three solutions were mixed to prepare coating solution β. Coating solution β was prepared according to the SiO 2 Solid content (converted value) and R of isocyanurate silane 2 Si(OH) 3 The solution was adjusted so that the mass ratio of the solid content (converted value) to the PVA solid content was 40 / 5 / 55.
[0399] <Preparation of Barrier Coating Liquid γ>
[0400] The coating liquid γ is prepared by mixing the following “aqueous polyurethane resin”: 40 to 75% by mass, “water-soluble polymer”: 10 to 40% by mass, and “silane coupling agent”: 5 to 20% by mass.
[0401] Aqueous polyurethane resin: Aqueous dispersion of an aqueous polyurethane resin containing an acid group-containing polyurethane resin and a polyamine compound, aqueous polyurethane dispersion "Takeluck (registered trademark) WPB-341" manufactured by Mitsui Chemicals, Inc., solid content: 30%.
[0402] Water-soluble polymer: polyvinyl alcohol having a saponification degree of 98 to 99% and a polymerization degree of 500 (trade name: Polyval PVA-105, manufactured by Kuraray Co., Ltd.).
[0403] Silane coupling agent: 3-glycidoxypropyltriethoxysilane (trade name: KBE-403, manufactured by Shin-Etsu Chemical Co., Ltd.).
[0404] (Example 45)
[0405] The adhesion layer-forming composition was applied to the substrate using a bar coater and dried at 50° C. Thus, an adhesion layer (anchor coating layer) having a thickness of 0.2 μm was formed. Next, a transparent deposition layer (silicon dioxide deposition layer) composed of silicon oxide having a thickness of 40 nm was formed using a vacuum deposition device using electron beam heating.
[0406] Next, the coating liquid α was applied on the vapor-deposited layer using a bar coater, and the coating liquid α was dried at 60° C. for 1 minute. Thus, a barrier coating layer with a thickness of 300 nm was formed on the vapor-deposited layer. In the above manner, a barrier layer having a substrate, an adhesion layer, a vapor-deposited layer, and a barrier coating layer was formed.
[0407] Next, a two-component curing type urethane adhesive (a) was applied on the barrier coating of the barrier layer to form an adhesive layer with a thickness of 3 μm. Next, a sealing layer was laminated by a dry lamination method via the adhesive layer. Thus, a laminate (gas barrier laminate) having a laminate structure of a substrate, a close-fitting layer, a vapor-deposited layer, a barrier coating, an adhesive layer, and a sealing layer was manufactured. The content of polypropylene in the obtained laminate was 90% by mass or more.
[0408] (Examples 46 to 50)
[0409] Laminated bodies of Examples 46 to 50 were respectively produced in the same manner as in Example 1 except that two-component curable urethane adhesives (b) to (f) were used instead of the adhesive (a).
[0410] (Examples 51 to 56)
[0411] Laminated bodies of Examples 51 to 56 were respectively produced in the same manner as in Examples 45 to 50 except that the coating liquid β was used instead of the coating liquid α.
[0412] (Examples 57 to 62)
[0413] Laminated bodies of Examples 57 to 62 were respectively produced in the same manner as in Examples 45 to 50 except that the coating liquid γ was used instead of the coating liquid α.
[0414] (Example 63)
[0415] After forming the barrier layer in the same manner as in Example 45, a two-component curing type urethane adhesive (a) is applied on the barrier coating of the barrier layer to form an adhesive layer with a thickness of 3 μm. Then, the outermost layer is laminated by dry lamination via the adhesive layer. Then, a two-component curing type urethane adhesive (a) is applied on the substrate of the barrier layer to form an adhesive layer with a thickness of 3 μm. Then, a sealing layer is laminated by dry lamination via the adhesive layer. Thus, a laminate (gas barrier laminate) having a laminated structure of an outermost layer, a second adhesive layer, a barrier coating, a vapor-deposited layer, a sealing layer, a substrate, an adhesive layer and a sealing layer is manufactured. The polypropylene content in the obtained laminate is 90% by mass or more.
[0416] (Examples 64 to 68)
[0417] Laminated bodies of Examples 64 to 68 were respectively produced in the same manner as in Example 63 except that two-component curable urethane adhesives (b) to (f) were used instead of the adhesive (a).
[0418] (Examples 69 to 74)
[0419] Laminated bodies of Examples 69 to 74 were respectively produced in the same manner as in Examples 63 to 68 except that the coating liquid β was used instead of the coating liquid α.
[0420] (Examples 75 to 80)
[0421] Laminated bodies of Examples 75 to 80 were respectively produced in the same manner as in Examples 63 to 68 except that the coating liquid γ was used instead of the coating liquid α.
[0422] (Comparative Examples 5 to 7)
[0423] Laminated bodies of Comparative Examples 5 to 7 were respectively produced in the same manner as in Example 45 except that the adhesives (g) to (i) were used instead of the adhesive (a).
[0424] (Comparative Examples 8 to 10)
[0425] Laminated bodies of Comparative Examples 8 to 10 were respectively produced in the same manner as in Example 51 except that the adhesives (g) to (i) were used instead of the adhesive (a).
[0426] (Comparative Examples 11 to 13)
[0427] Laminated bodies of Comparative Examples 11 to 13 were respectively produced in the same manner as in Example 57 except that the adhesives (g) to (i) were used instead of the adhesive (a).
[0428] (Comparative Examples 14 to 16)
[0429] Laminated bodies of Comparative Examples 14 to 16 were respectively produced in the same manner as in Example 63 except that the adhesives (g) to (i) were used instead of the adhesive (a).
[0430] (Comparative Examples 17 to 19)
[0431] Laminated bodies of Comparative Examples 17 to 19 were respectively produced in the same manner as in Example 69 except that the adhesives (g) to (i) were used instead of the adhesive (a).
[0432] (Comparative Examples 20 to 22)
[0433] Laminated bodies of Comparative Examples 20 to 22 were respectively produced in the same manner as in Example 75 except that the adhesives (g) to (i) were used instead of the adhesive (a).
[0434] (Comparative Example 23)
[0435] A laminate of Comparative Example 19 was produced in the same manner as in Example 45 except that a PET film (thickness: 20 μm) was used as the substrate instead of the OPP film.
[0436] (Comparative Example 24)
[0437] A laminate of Comparative Example 20 was produced in the same manner as in Comparative Example 5 except that a PET film (thickness: 20 μm) was used as the substrate instead of the OPP film.
[0438] <Method for measuring thermal shrinkage of substrate>
[0439] The heat shrinkage of the substrate contained in the barrier layer is measured according to the following procedures. The results of the measurement of the heat shrinkage of the substrate in Examples 45 to 50 and Comparative Examples 5 to 7 are shown in Table 8 below. The results of the measurement of the heat shrinkage of the substrate in Examples 51 to 56 and Comparative Examples 8 to 10 are shown in Table 9 below. The results of the measurement of the heat shrinkage of the substrate in Examples 57 to 62 and Comparative Examples 11 to 13 are shown in Table 10 below. The results of the measurement of the heat shrinkage of the substrate in Examples 63 to 68 and Comparative Examples 14 to 16 are shown in Table 11 below. The results of the measurement of the heat shrinkage of the substrate in Examples 69 to 74 and Comparative Examples 17 to 19 are shown in Table 12 below. The results of the measurement of the heat shrinkage of the substrate in Examples 75 to 80 and Comparative Examples 20 to 22 are shown in Table 13 below. The results of the measurement of the heat shrinkage of the substrate in Comparative Examples 23 and 24 are shown in Table 14 below.
[0440] (a) If Figure 8 As shown, the substrate to be measured is cut into 200 mm×200 mm to prepare a measurement sample 500 .
[0441] (b) If Figure 8 As shown, two straight lines L1 and L2 having a length of 120 mm or more and parallel to the TD direction of the measurement sample 500 are written at an interval of 100 mm.
[0442] (c) Figure 8 As shown, two straight lines L3 and L4 having a length of 120 mm or more and parallel to the MD direction of the measurement sample 500 are written at an interval of 100 mm.
[0443] (d) If Figure 8 As shown, scales N1 to N7 are written at 7 positions at 20 mm intervals on the straight line L1. Scales are also written on the straight lines L2 to L4. At this time, when the scales N1 to N7 of the straight line L1 and the scales N1 to N7 of the straight line L2 are connected by a straight line, the scale positions of the straight lines L1 and L2 are aligned in such a way that the straight line is parallel to the MD direction. In addition, when the scales N1 to N7 of the straight line L3 and the scales N1 to N7 of the straight line L4 are connected by a straight line, the scale positions of the straight lines L3 and L4 are aligned in such a way that the straight line is parallel to the TD direction.
[0444] (e) The measurement sample 500 on the Teflon (registered trademark) sheet is placed on a glass plate in an oven heated to a predetermined temperature (150°C or 160°C) and heated for 15 minutes. After heating, the measurement sample 500 is taken out of the oven and left at room temperature (25°C) for 30 minutes.
[0445] (f) The linear distance between the scale N1 of the straight line L1 (the intersection of L1 and N1) and the scale N1 of the straight line L2 (the intersection of L2 and N1) is taken as the MD direction length, and the measurement is performed before and after heating, and the MD direction heat shrinkage rate is calculated by the following formula (1). Similarly, the MD direction heat shrinkage rate of each position of the scale N1 to N7 is calculated, and their average value is taken as the MD direction heat shrinkage rate of the measurement sample 500.
[0446] MD direction heat shrinkage rate (%) = (MD direction length before heating - MD direction length after heating) / MD direction length before heating × 100 (1)
[0447] <Steaming treatment>
[0448] The laminates prepared in each of the examples and comparative examples were used to prepare packaging bags with four sides as sealed portions. The packaging bags were filled with water as the content and then subjected to retort sterilization treatment at 130° C. for 60 minutes.
[0449] <Measurement of Hardness of Adhesive Layer>
[0450] In Examples 45 to 62 and Comparative Examples 5 to 13, a laminate as a part of a packaging bag after retorting was cut out. Then, an epoxy adhesive (manufactured by Conisy Co., Ltd., trade name: Bond E-Set) was applied to the base layer of the cut laminate. Then, the laminate was attached to a glass plate via the epoxy adhesive, thereby forming a sample having a laminate smoothly fixed on the glass plate. In addition, in Examples 63 to 80 and Comparative Examples 14 to 22, an epoxy adhesive (manufactured by Conisy Co., Ltd., trade name: Bond E-Set) was applied to the outermost layer of the laminate after retorting, respectively, to form a sample.
[0451] After the epoxy adhesive is cured, a sample is set on an oblique cutting device (manufactured by Dypro Instruments Co., Ltd., trade name: SAICASDN-GS). Next, after a diamond cutting blade with a V-shaped front end is installed on the oblique cutting device, a side cut line is formed on the surface of the sealing layer at a width interval of 1 mm. Next, a diamond knife with a blade width of 1 mm, a front angle of 20 degrees, and a back angle of 10 degrees is brought into contact with the surface of the sealing layer with a load of 0.05 N, and the sealing layer is obliquely cut under the conditions of a horizontal speed of 50 μm / s and a vertical speed of 1 μm / s. At this time, first, after the cutting depth reaches 55 μm, 10 mm is cut horizontally. Then, fine cutting is performed with a cutting depth of 1 μm under the conditions of a horizontal speed of 50 μm / s and a vertical speed of 1 μm / s. Observe the exposed surface after cutting, and add the number of fine cutting times as needed until the exposed surface of the desired bonding layer is obtained. As described above, the preparation for measuring the hardness of the adhesive layer after the retort treatment by the nanoindentation method (ie, the preparation for exposing the adhesive layer) is completed.
[0452] Next, as a device for measuring the hardness of the adhesive layer by nanoindentation, Hysitron TI-Premier (trade name) manufactured by Bruka Japan Co., Ltd. was used. In addition, as an indenter, a Berkovich-type diamond indenter manufactured by Bruka Japan Co., Ltd. was used. Then, after the sample with the adhesive layer exposed was set on the above-mentioned device, the indentation speed was set to 100nm / second and the test depth was set to 125nm in the displacement control mode, and the indenter was pressed into the sample at room temperature (25°C). Then, after the maximum displacement was maintained for 2 seconds, it was unloaded at a speed of 50nm / second. The surface load was set to 1μN, and the surface correction was performed using the TriboScan software. The measurement position is to observe the optical microscope image, and the sample surface, that is, the exposed surface of the adhesive layer (the position 1 / 4 of the distance from the sealant side when the distance between the sealing layer and the substrate layer is divided into 4 equal parts on the exposed surface) is designated at 30 points at intervals of more than 30 μm, and the measurement is performed using the nanoindentation method. The hardness of the adhesive layer is calculated by first pre-testing fused quartz as a standard sample and calibrating the relationship between the contact depth and contact projection area between the indenter and the sample. Then, the unloading curve in the area of 20 to 95% of the maximum load during unloading is analyzed using the Oliver-Pharr method, and the hardness is calculated. The measurement results of the hardness of the adhesive layer in Examples 45 to 80 and Comparative Examples 5 to 24 are shown in the following Tables 8 to 14.
[0453] (Oxygen permeability measurement)
[0454] The oxygen permeability (OTR) of the laminate after steaming treatment was measured. The measurement was carried out using an oxygen permeability measuring device (modern control company, OXTRAN 2 / 20) at a temperature of 30 ° C and a relative humidity of 70%. The OTR measurement method is based on JIS K-7126, B method (isobaric method) and ASTM D3985-81. The measured value of OTR is expressed in units of [cc / m 2 The results of OTR measurement of Examples 45 to 80 and Comparative Examples 5 to 24 are shown in Tables 8 to 14 below, respectively.
[0455] Table 8
[0456]
[0457] Table 9
[0458]
[0459] Table 110
[0460]
[0461] Table 11
[0462]
[0463] Table 12
[0464]
[0465] Table 13
[0466]
[0467] Table 114
[0468]
[0469] In any of Tables 8 to 14, the greater the hardness of the adhesive layer, the higher the measured result of the oxygen permeability. However, the absolute value of the oxygen permeability varies greatly depending on whether the heat shrinkage rate of the substrate is 1% or more. Specifically, when a substrate with a heat shrinkage rate of 1% or more is used, as shown in Tables 8 to 13, the oxygen permeability when the hardness of the adhesive layer is 0.9 MPa or more is higher than the oxygen permeability when the hardness of the adhesive is 0.8 MPa. In addition, the oxygen permeability when the hardness of the adhesive layer is 0.9 MPa or more is at least 3.5 or more. In contrast, when a substrate with a heat shrinkage rate of less than 1% is used, as shown in Table 7, the difference in oxygen permeability when the hardness of the adhesive layer is 0.9 MPa or more and the oxygen permeability when the hardness of the adhesive is 0.8 MPa can be said to be the degree of error.
[0470] In Tables 8 to 10 and Tables 11 to 13, the oxygen permeability of the Examples and Comparative Examples using the coating liquid β or the coating liquid γ is lower than that of the Examples and Comparative Examples using the coating liquid α. In addition, the oxygen permeability of the Examples and Comparative Examples having the outermost layer is lower than that of the Examples and Comparative Examples not having the outermost layer.
[0471] Explanation of symbols
[0472] 1 substrate layer, 2, 43 vapor-deposited layer, 3 gas barrier coating layer, 10a, 10b gas barrier film, 11 first surface layer, 12 core layer, 13 second surface layer, 20, 30 packaging film, 22 outer film (outermost layer), 23, 50 sealing layer, 24, 60 adhesive layer, 25, 60A second adhesive layer, 35, 35A laminate (packaging film), 40 barrier layer (gas barrier film), 41 substrate (substrate layer), 44 barrier coating (gas barrier coating layer), 70 outermost layer, 100 packaging bag.
Claims
1. A gas barrier film comprising, in this order, a substrate layer containing a polypropylene resin, a vapor-deposited layer containing an inorganic oxide, and a gas barrier coating layer, The base material layer includes a first surface layer and a core layer, and the vapor-deposited layer is formed on the first surface layer side. The hardness of the first surface layer measured by nanoindentation method is 0.02-0.15 GPa, the hardness of the core layer is above 0.07 GPa, and the hardness of the core layer is greater than that of the first surface layer.
2. The gas barrier film according to claim 1, wherein The first skin layer contains a propylene-α-olefin copolymer.
3. The gas barrier film according to claim 1 or 2, wherein The ratio of the thickness of the first skin layer to the thickness of the core layer is 1 / 100 to 1 / 5.
4. The gas barrier film according to claim 1 or 2, wherein The complex elastic modulus of the first surface layer measured by nanoindentation method is 1.2 to 2.5 GPa, and the complex elastic modulus of the core layer is greater than 2.0 GPa.
5. The gas barrier film according to claim 1 or 2, wherein The inorganic oxide contains at least one of aluminum oxide and silicon oxide.
6. The gas barrier film according to claim 1 or 2, wherein The gas barrier coating layer is formed of a cured product of a composition containing a water-soluble polymer having a hydroxyl group and at least one selected from a metal alkoxide, a silane coupling agent, and hydrolyzates thereof.
7. The gas barrier film according to claim 1 or 2, wherein An anchor coating layer is further provided between the substrate layer and the vapor deposited layer.
8. The gas barrier film according to claim 1 or 2, wherein The base material layer includes the first surface layer, the core layer, and the second surface layer in this order.
9. The gas barrier film according to claim 8, wherein The second skin layer contains a propylene-α-olefin copolymer.
10. The gas barrier film according to claim 9, wherein The hardness of the second surface layer measured by nanoindentation method is 0.02 to 0.15 GPa.
11. The gas barrier film according to claim 1 or 2, wherein The thickness of the evaporated layer is 5nm-80nm.
12. A packaging film comprising: The gas barrier film according to claim 1, a sealing layer overlapping the gas barrier coating layer, and an adhesive layer for bonding the gas barrier coating layer and the sealing layer together; in, After the packaging film is subjected to a retort treatment, the hardness of the adhesive layer measured by a nanoindentation method is 0.1 MPa or more and less than 0.9 MPa.
13. The packaging film according to claim 12, wherein: Before the retort treatment, the hardness of the adhesive layer measured by a nanoindentation method is 1.0 MPa or more.
14. The packaging film according to claim 12 or 13, wherein: The thickness of the adhesive layer is 0.5 μm to 10 μm.
15. The packaging film according to claim 12 or 13, wherein: The substrate layer and the sealing layer are polyolefin films respectively. The proportion of the total mass of the polyolefin in the packaging film is 90 mass % or more.
16. The packaging film according to claim 12 or 13, wherein The substrate layer is a stretched polypropylene film, The sealing layer is an unstretched polypropylene film.
17. The packaging film according to claim 12 or 13, further comprising an outermost layer overlapping the base layer, and a second adhesive layer for bonding the outermost layer and the base layer together. The adhesive layer bonds the base material layer and the sealing layer. The second adhesive layer bonds the substrate and the outermost layer.
18. The packaging film according to claim 17, wherein After the outermost layer is exposed to 120° C. for 15 minutes, the heat shrinkage of the outermost layer in the MD direction calculated by the following formula (1) is 1% or more. After the packaging film is subjected to a retort treatment, the hardness of the second adhesive layer measured by a nanoindentation method is 0.1 MPa or more and less than 0.9 MPa. Heat shrinkage ratio in MD direction (%)=(length in MD direction before heating−length in MD direction after heating) / length in MD direction before heating×100(1).
19. A packaging bag, which is a bag-made product of the packaging film according to claim 12 or 13.
Citation Information
Patent Citations
Multi-layer polypropylene film
JP1988290743A
Polypropylene based film
JP1988291929A
Wear-resisting cigarette barrel packaging film and fabrication method thereof
CN103029390A
Polypropylene-based laminate film
CN111132831A
Laminates with gas-barrier property
CN1922005A